High-purity 4-(2-bromoethyl)benzenesulfonic acid, high-purity styrenesulfonic acids derived therefrom, and polymers thereof, and methods for producing the same
Patent Information
- Application Number
- JP2023092119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-05
- Publication Date
- 2025-02-21
AI Technical Summary
Existing methods for producing styrene sulfonic acids and polymers fail to adequately reduce unstable bonded bromine impurities, leading to increased bromide ion concentration over time, which is problematic for long-term stability and storage.
The production process involves controlling the reaction conditions of 4-(2-bromoethyl)benzenesulfonic acid to minimize nuclear brominated forms, using specific concentrations of sulfonating agents, iron, hydrogen bromide, and water, and employing purification methods like cation exchange and recrystallization to achieve high purity.
The resulting styrene sulfonic acids and polymers exhibit significantly reduced unstable bonded bromine, ensuring long-term stability and suitability for electronic materials applications.
Smart Images

Figure 2023133284000001 
Figure 2023133284000002 
Figure 2023133284000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to high-purity 4-(2-bromoethyl)benzenesulfonic acid having reduced nuclear bromine content, high-purity styrenesulfonic acids and polymers thereof having reduced bound bromine content derived therefrom, and methods for producing the same. [Background technology]
[0002] Styrene sulfonic acids and polystyrene sulfonic acids derived therefrom are functional monomers and polymers thereof that are used in fuel cell membranes, polymer solid electrolytes and additives for secondary batteries, dispersants and dopants for conductive polymers and carbon nanotubes, semiconductor cleaners, electron acceptors and thermal acid generators for organic EL devices, and thermal acid generators and protective films for photoresists (see, for example, Patent Documents 1 to 5). Because they are primarily used in the electronic materials field, there is a demand for high-purity styrene sulfonic acids and polymers thereof that have as little impurities as possible, such as halogens, which cause metal corrosion (see, for example, Patent Document 6).
[0003] Among styrene sulfonic acids, styrene sulfonate esters are oil-soluble liquid monomers that can be easily copolymerized with oil-soluble monomers or used in coating processes to form polymer coatings on the surfaces of various substrates or to produce polymer electrolyte membranes, making them particularly valuable for the above applications. Furthermore, styrene sulfonate salts such as amine salts and lithium salts of styrene sulfonate are highly soluble in water and aprotic polar solvents, making them suitable for coating processes, and also enabling the production of aqueous polystyrene sulfonic acid solutions without the use of organic solvents (see, for example, Patent Document 7). Styrene sulfonate esters can be produced by the following method (for example, Non-Patent Document 1): A styrene sulfonate salt such as sodium styrene sulfonate is reacted with thionyl chloride to form styrene sulfonyl chloride, which is then esterified using a base such as potassium hydroxide and an alcohol.
[0004] [ka]
[0005] One application of polymerizable styrene sulfonate esters, which are vinyl monomers, is polystyrene sulfonate with controlled molecular weight distribution for producing aqueous colloids of conductive polymers (see, for example, Patent Document 2). For example, it has been reported that an aqueous polystyrene sulfonate solution can be produced by subjecting ethyl styrene sulfonate to living radical polymerization, hydrolyzing the ester groups with sodium hydroxide, and then removing metal cations, low-molecular-weight impurities, and unreacted monomers using a cation exchange resin and an ultrafiltration membrane.
[0006] [ka]
[0007] Polystyrene sulfonate can also be produced by other methods. For example, styrene sulfonate monohydrate The sodium was radically polymerized in water, sodium hydroxide was added, and the mixture was heated at 60°C. As mentioned above, by purifying using a cation exchange resin and an ultrafiltration membrane, polystyrene It has been reported that an aqueous sulfonic acid solution can be produced (for example, Patent Document 7).
[0008] [ka]
[0009] Polystyrene sulfonic acid can also be produced by another method. This is a method of sulfonating polystyrene in an inert solvent (for example, Patent Document 8). The manufacturing method has the advantage of preventing the inclusion of alkali metal halides, but the polymer composition and The disadvantages are that the degree of freedom in polymer design is small, such as molecular weight, and branched structures are easily generated. be. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2017-43700 A [Patent Document 2] Japanese Patent Application Laid-Open No. 2011-213823 [Patent Document 3] International Publication No. WO2015 / 114966 [Patent Document 4] International Publication No. WO2007 / 099808 [Patent Document 5] Japanese Patent Application Laid-Open No. 2004-177666 [Patent Document 6] Japanese Patent Application Publication No. 5-326477 [Patent Document 7] Japanese Patent Application Laid-Open No. 2009-1624 [Patent Document 8] Japanese Patent Application Publication No. 8-299777 [Non-patent literature]
[0011] [Non-Patent Document 1] H. Okamura et al.; Polymer, Vol. 43, pp. 3155-3162, 2002 Summary of the Invention [Problem to be solved by the invention]
[0012] As described above, there has been a demand for high-purity styrene sulfonic acids and polymers thereof in which halogen impurities have been reduced as much as possible, and reducing halogen impurities has been an issue.
[0013] Patent Document 7 discloses polystyrene sulfonate having a number-average molecular weight of 50,000 to 1,000,000, a total residual amount of bromine and chlorine of 500 ppm (by mass) or less, and a residual amount of styrene sulfonic acid monomer of 1% by mass or less. After polymerizing sodium styrene sulfonate, the resulting polystyrene sulfonate is treated with an alkali such as ammonia or sodium hydroxide to liberate bromine and chlorine, which are then removed by ethanol precipitation or ultrafiltration to obtain an aqueous solution of polystyrene sulfonate from which bromine, chlorine, and unreacted sodium styrene sulfonate have been removed (Claim 1 and Paragraph 0030). However, the bromine and chlorine sources are not specifically disclosed, leaving the details unclear.
[0014] Polystyrene sulfonic acid was prepared using the same method as described above, and the halogen concentration in the aqueous solution was analyzed by ion chromatography. It was indeed possible to achieve a bromide ion concentration of less than 1 ppm in the fresh aqueous solution immediately after production. However, the inventors conducted a detailed investigation into the long-term stability of this polystyrene sulfonic acid aqueous solution and found that the bromide ion concentration in the aqueous solution increased significantly over time, even under mild conditions, leaving a problem. This suggests the presence of unstable bound bromine, which cannot be removed by the purification method described above and has not been reported previously. It has previously been difficult to clarify the cause of the increase in bromide ion concentration over time and to obtain polystyrene sulfonic acid that can be stored for a long period of time.
[0015] Regarding bound bromine in sodium styrenesulfonate, the presence of sodium bromostyrenesulfonate has been reported (for example, International Publication No. WO2014 / 061357). This patent discloses high-purity sodium styrenesulfonate with a sodium bromostyrenesulfonate content of 0.01% (area basis measured by high-performance liquid chromatography) (paragraph 0080 of the patent publication).
[0016] That is, Example 2 of the publication of the patent contains the following description as Evaluation Example 2 of the production of high-purity sodium p-styrenesulfonate and sodium PSS, and its use as a synthetic starch for a clothing ironing agent: Note that the relative values based on the area of the peak areas of the compounds (a) to (e) measured by high-performance liquid chromatography described below are (a): sodium orthostyrenesulfonate, (b): sodium β-bromoethylbenzenesulfonate, (c): sodium metastyrenesulfonate, (d): sodium bromostyrenesulfonate, and (e): sodium β-hydroxyethylbenzenesulfonate. <Production of high-purity sodium p-styrenesulfonate> A jacketed stainless steel reactor equipped with a stirrer was charged with 1,000 g of high-purity sodium p-styrenesulfonate obtained in Example 1, 1 g of sodium nitrite, 20 g of caustic soda, and 950 g of pure water, and the mixture was stirred at 60°C for 1 hour under a nitrogen atmosphere. Thereafter, the mixture was cooled to room temperature over 3 hours, and then subjected to solid-liquid separation using a centrifuge to obtain 899 g of a wet cake of high-purity sodium p-styrenesulfonate. The purity of the high-purity sodium p-styrenesulfonate was 89.1 wt%, the water content was 8.2 wt%, the iron content was 0.58 μg / g, the sodium bromide content was 0.20 wt%, and the contents of organic impurities such as isomers were (a) 0.05%, (b) 0.00%, (c) 1.34%, (d) 0.01%, and (e) 0.01%. The median diameter of the sodium p-styrenesulfonate was 63 μm, the content of small particles less than 10.00 μm was 2.0%, the angle of repose was 49°, and the dissolution time in water was 155 seconds. The WI value of the sodium p-styrenesulfonate was 95.5, the YI value was 2.9, and the APHA value of a 15 wt% aqueous solution was 15, demonstrating a significantly superior hue compared to the conventional product (Comparative Example 1). Furthermore, although the reason is unclear, it is clear that even though the iron content is at the same level as in Example 1, the hue is further improved by reducing impurities such as sodium bromide and isomers.
[0017] The problem to be solved in this patent is to improve the hue of sodium p-styrenesulfonate and sodium PSS (sodium polystyrenesulfonate), and the hue is improved through a synergistic effect achieved by simultaneously reducing the iron content and various organic impurities that may be contained in sodium p-styrenesulfonate. Specifically, the iron content in an aqueous solution of 4-(2-bromoethyl)benzenesulfonic acid, the precursor of sodium p-styrenesulfonate, is removed by cation exchange treatment, and the resulting sodium p-styrenesulfonate is purified by recrystallization to remove the organic impurities. However, there is no mention of the effect of sodium bromostyrenesulfonate on the hue. On the other hand, the problem to be solved by the present invention is the reduction of halogen impurities, which is strongly demanded in the field of electronic materials, and in particular, the reduction of organic halogen impurities, that is, bonded halogens, which are difficult to remove. It is true that in the above patent document, it appears that the reduction of sodium bromostyrenesulfonate reduces the bound halogen. However, when the present inventors analyzed the total halogen content in the high-purity sodium styrenesulfonate using combustion decomposition ion chromatography or other methods, they detected a bromine content of over 400 ppm, which is at least 10 times the value estimated by the high-performance liquid chromatography. Therefore, they actually prepared an aqueous polystyrene sulfonic acid solution from the high-purity sodium styrenesulfonate and examined its stability, and found that the bromine ion concentration significantly increased over time. For these reasons, there has been a demand for high-purity styrene sulfonic acids and polymers thereof with as little unstable bound bromine as possible, as well as a method for producing the same. To achieve this, it is necessary to not only look at the bromine content, but also to examine in detail the process and the chemical structure in which the bromine content, such as bound bromine, is contained.
[0018] The present invention has been made in view of the above problems, and an object of the present invention is to provide styrenesulfonic acids and polymers thereof having reduced unstable bound bromine, and methods for producing the same. [Means for solving the problem]
[0019] To solve the above problems, we focused on 4-(2-bromoethyl)benzenesulfonic acid (hereinafter sometimes abbreviated as BEBS), a precursor of styrenesulfonic acids, and conducted extensive research. As a result, we discovered that BEBS contains impurities, including previously unreported compounds such as 2-bromo-4-(2-bromoethyl)benzenesulfonic acid, which are nuclear brominated forms of BEBS (hereinafter sometimes abbreviated as nuclear brominated BEBS). Furthermore, we discovered that when sulfonating 4-(2-bromoethyl)benzene using a sulfonating agent, by controlling the iron, hydrogen bromide, and water concentrations that may be present in the reaction system to below certain levels and conducting the sulfonation reaction at a specific sulfonating agent concentration and molar ratio to BEBS, high-purity BEBS with a low content of nuclear brominated BEBS can be produced without sacrificing productivity. Furthermore, we discovered that the bound bromine in the styrenesulfonic acids and their polymers derived from the high-purity BEBS can be significantly reduced. This finding led to the completion of the present invention.
[0020] In other words, if it is known at what stage and in what form bound bromine in styrenesulfonic acids (and their polymers) is generated in the process of producing styrenesulfonic acids from styrene, it is thought that conditions for suppressing its generation can be found. The reaction process from styrene to sodium styrenesulfonate via 2-bromoethylbenzene and 4-(2-bromoethyl)benzenesulfonic acid is shown below. It was initially thought that the liberated bromine produced bound bromine in styrenesulfonic acids (and their polymers) during the vinylation (removal of NaBr) reaction step, in which an alkali such as NaOH was added to 4-(2-bromoethyl)benzenesulfonic acid at a high temperature of 70-90°C. However, through investigations by the present inventors, it was found that bound bromine (in this case, nuclear-brominated BEBS) is produced at least in the process of sulfonating 2-bromoethylbenzene to produce 4-(2-bromoethyl)benzenesulfonic acid. Therefore, the present inventors have arrived at the idea that by identifying the structure of the molecule that is produced as bound bromine and at what stage the molecule is produced, it is possible to suppress the inclusion of bound bromine in styrene sulfonic acids (and their polymers).
[0021] [ka]
[0022] The term "nuclear brominated BEBS" as used herein refers to BEBS in which at least one bromine atom is bonded to the benzene ring of BEBS via a covalent bond (general formula (1) below), and examples thereof include those represented by the following general formula (1') in which one bromine atom is bonded to the benzene ring. Here, the position at which the bromine atom is bonded to the benzene ring is not particularly limited, and examples of BEBS in which one bromine atom is bonded to the benzene ring include 2-bromo-4-(2-bromoethyl)benzenesulfonic acid as shown in Figure 1, which will be described later. Furthermore, the term "bound bromine" refers to bromine bonded via a covalent bond to a styrenesulfonic acid having a polymerizable vinyl group as shown below, and includes at least one bromine bonded to the benzene ring of the styrenesulfonic acid (general formula (2) below). For example, one bromine bonded to the benzene ring is represented by the following general formula (2'). Here, the position at which the bromine atom is bonded to the benzene ring is not particularly limited, and an example of a compound in which one bromine atom is bonded to the benzene ring is 2-bromo-4-styrenesulfonic acid. By reducing the total bonded bromine, the unstable bromine content, which was a problem, was reduced. [ka] (In formula (1), n is an integer of 1 to 3.) [ka] [ka] (In formula (2), R 1 is defined as in the following general formula (B), and n is an integer of 1 to 3. [ka] (In formula (2'), R 1 is the same as the definition of general formula (B) below.
[0023] That is, the present invention relates to the following inventions. [1] High-purity 4-(2-bromoethyl)benzenesulfonic acid, in which the content of nuclear brominated 2-bromoethylbenzenesulfonic acid represented by the following general formula (A) is 0.10% or less relative to the content of 4-(2-bromoethyl)benzenesulfonic acid (wherein the peak area % is determined by liquid chromatography (LC), and the peak area % of nuclear brominated 2-bromoethylbenzenesulfonic acid is calculated when the peak area of 4-(2-bromoethyl)benzenesulfonic acid is taken as 100%). [ka] [2] The high-purity 4-(2-bromoethyl)benzenesulfonic acid according to item [1], wherein the brominated 2-bromoethylbenzenesulfonic acid is 2-bromo-4-(2-bromoethyl)benzenesulfonic acid. [3] The high-purity 4-(2-bromoethyl)benzenesulfonic acid according to item [1] or [2], wherein the purity of the 4-(2-bromoethyl)benzenesulfonic acid determined by liquid chromatography (LC) is 93 area % or more. [4] A method for producing 4-(2-bromoethyl)benzenesulfonic acid, comprising continuously supplying 2-bromoethylbenzene or an organic solvent solution of 2-bromoethylbenzene, and sulfuric anhydride or an organic solvent solution of sulfuric anhydride to a reactor, wherein the iron content of the 2-bromoethylbenzene and the organic solvent is controlled to 5 μg / g or less, the hydrogen bromide content is controlled to 100 ppm or less, and the water content is controlled to 1000 ppm or less, the weight percentage of sulfuric anhydride supplied to the total reaction solution in the reactor is maintained at 5.00 wt% to 20.00 wt%, and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene in the reactor is maintained at 0.50 to 2.00. The method for producing high-purity 4-(2-bromoethyl)benzenesulfonic acid according to any one of [1] to [3], [5] A method for producing 4-(2-bromoethyl)benzenesulfonic acid, comprising continuously supplying sulfuric anhydride or an organic solvent solution of sulfuric anhydride to 2-bromoethylbenzene or an organic solvent solution of 2-bromoethylbenzene, wherein the iron contents of the 2-bromoethylbenzene and the organic solvent are controlled to 5 μg / g or less, the hydrogen bromide contents to 100 ppm or less, and the water contents to 1,000 ppm or less, the weight percentage of sulfuric anhydride supplied to the total reaction solution in the reactor is kept to 20.00 wt % or less, and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene in the reactor is kept to 2.00 or less. [6] The method according to item [4] or [5], wherein the organic solvent is one or more organic solvents selected from the group consisting of halogenated solvents, nitrated solvents, and aliphatic hydrocarbons. [7] The method according to any one of [4] to [6], wherein the sulfuric anhydride contains 5% by weight to 10% by weight of acetic acid or acetic anhydride relative to the sulfuric anhydride. [8] The method according to any one of items [4] to [7], wherein the sulfuric anhydride or the solution of sulfuric anhydride in an organic solvent is continuously supplied over a period of 0.5 to 7 hours. [9] The method according to any one of items [4] to [8], wherein the reaction temperature is 10 to 60°C and the reaction time is 0.5 to 10 hours.
[10] The method according to any one of [4] to [9], wherein the reaction solution is continuously withdrawn during the reaction.
[11] High-purity styrene sulfonic acids represented by the following general formula (B), having a bound bromine content of 400 ppm or less as determined by combustion decomposition ion chromatography (CIC): [ka] [In the formula, R 1 represents the following general formula (C), the following general formula (D), an amino group, or a chlorine atom. [ka] [In the formula, R 2 represents a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a hydrogen atom, an alkali metal, a substituted or unsubstituted ammonium cation, or a substituted or unsubstituted phosphonium cation. [ka] [In the formula, R 3 represents a substituted or unsubstituted alkyl group, a hydrogen atom, an alkali metal, or a substituted or unsubstituted ammonium cation; R 4 represents a trifluoromethylsulfonyl group, a perfluorobutylsulfonyl group, a fluorosulfonyl group, a trifluoromethylacetyl group, or a 4-ethenylphenylsulfonyl group. In general formula (B), R 1 When is an amino group, the amino group may be any of a primary amino group, a secondary amino group, a tertiary amino group, and a quaternary amino group, except for groups of general formula (D).
[12] The styrene sulfonic acids represented by the following general formula (B') are sodium 4-styrene sulfonate, lithium 4-styrene sulfonate, potassium 4-styrene sulfonate, ammonium 4-styrene sulfonate, N,N-dimethylcyclohexylamine 4-styrene sulfonate, trioctylamine 4-styrene sulfonate, 4-styrene sulfonyl chloride, 4-styrene sulfonamide, ethyl 4-styrene sulfonate, neopentyl 4-styrene sulfonate, 4-styrene sulfonyl(trifluoromethylsulfonylimide), 4-styrene sulfonyl(perfluorobutylsulfonylimide), 4-styrene sulfonyl(fluorosulfonylimide), or lithium bis(4-styrenesulfonyl)imide High-purity styrene sulfonic acids having a bound bromine content of 400 ppm or less as determined by combustion decomposition ion chromatography (CIC). [ka] (In formula (B'), R 1 is the same as defined in the general formula (B) above.
[13] A method for producing styrenesulfonic acids, using the high-purity 4-(2-bromoethyl)benzenesulfonic acid described in [1] or the high-purity 4-(2-bromoethyl)benzenesulfonic acid obtained by the production method described in [4] or [5].
[14] Polystyrene sulfonic acids having the following repeating structural unit (E), or polystyrene sulfonic acids having the following repeating structural unit (E) and the following repeating structural unit (F), wherein a 10 wt % aqueous solution of the polystyrene sulfonic acids is kept at 70°C for 20 days, and the bromine ion concentration in the aqueous solution is 30 ppm or less, and the polystyrene sulfonic acids have reduced bound bromine. [ka] [In the formula, R 1 is R in the general formula (B) described in
[11] above. 1 Same as above. [ka] [In the formula, Q represents a repeating structural unit derived from a vinyl monomer copolymerizable with styrenesulfonic acids.]
[15] The polystyrene sulfonic acids according to item
[14] , wherein the number average molecular weight of the polystyrene sulfonic acids is 500 to 5,000,000.
[16] The polystyrene sulfonic acids according to item
[14] or
[15] , wherein Q in the repeating structural unit (F) contains a repeating structural unit derived from a vinyl monomer that is one or a combination of two or more selected from the group consisting of (meth)acrylic acid, (meth)acrylic acid esters, (meth)acrylamide, N-substituted maleimides, styrenes, and vinylpyridines.
[17] The polystyrene sulfonic acids according to any one of items
[14] to
[16] , wherein Q in the repeating structural unit (F) comprises a repeating structural unit derived from a crosslinkable monomer that is one or a combination of two or more selected from the group consisting of substituted styrenes, (meth)acrylic acid esters, (meth)acrylamides, and N-substituted maleimides.
[18] A method for producing polystyrene sulfonic acids, comprising polymerizing the high-purity styrene sulfonic acids according to item
[11] or the high-purity styrene sulfonic acids obtained by the production method according to item
[13] . The method for producing polystyrene sulfonic acids according to any one of items
[14] to
[17] .
[19] The polystyrene sulfonic acids according to any one of items
[14] to
[17] , wherein the bromine ion concentration in a 10 wt% aqueous solution is 10 ppm or less when the solution is kept at 70°C for 20 days.
[20] A method for producing polystyrene sulfonic acids according to item
[19] , characterized in that the polystyrene sulfonic acids according to items
[14] to
[17] are chemically treated by the following step (i) or (ii): (i) adding an alkali or an alkali and a reducing agent to the solution of polystyrene sulfonic acids, and heat-treating the solution at 90°C to 110°C for 5 to 30 hours while maintaining the solution pH ≥ 13, and then purifying the polymer; (ii) adding a reducing agent and a palladium catalyst to the solution of polystyrene sulfonic acids, heat treating the solution at 80°C to 110°C for 5 to 30 hours, and then purifying the polymer;
[21] An aqueous solution composition of polystyrene sulfonic acids, wherein the content of the polystyrene sulfonic acids according to item
[14] or
[19] or the polystyrene sulfonic acids obtained by the production method according to item
[18] is 1% by weight to 60% by weight, and the content of a phenolic antioxidant relative to the pure content of the polystyrene sulfonic acids is 20 ppm to 2,000 ppm.
[22] Item
[21] , wherein the phenolic antioxidant is at least one selected from the group consisting of 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 4-tert-butylcatechol, hydroquinone, and methoxyhydroquinone. The polystyrene sulfonic acid aqueous solution composition according to item
[21] . [Effects of the Invention]
[0024] The high-purity 4-(2-bromoethyl)benzenesulfonic acid and high-purity styrenesulfonic acids and polymers derived therefrom of the present invention have less bound bromine, such as in nuclear brominated products, than conventional products, and are inhibited from liberating bromine over time. Therefore, they are extremely useful in electronic material applications such as secondary batteries, capacitors, polymer solid electrolytes, conductive polymers, organic EL devices, photoresists, and semiconductor cleaning agents. [Brief explanation of the drawings]
[0025] [Figure 1] 1 is an enlarged HPLC chart of the aqueous BEBS solution obtained by the conventional method described in Comparative Example 4. The horizontal axis represents elution time (minutes) and the vertical axis represents peak intensity (mV). In the figure, (A) represents the peak of 4-(2-hydroxyethyl)benzenesulfonic acid, (B) represents the peak of the para-BEBS isomer, (C) represents the peak of the ortho-BEBS isomer, (D) represents the peak of 4-(1-bromoethyl)benzenesulfonic acid, and (E) represents the peak of 2-bromo-4-(2-bromoethyl)benzenesulfonic acid (nuclear-brominated BEBS). [Figure 2] 2 is an enlarged HPLC chart of the BEBS aqueous solution obtained by the method of the present invention described in Example 1. The horizontal axis represents elution time (minutes) and the vertical axis represents peak intensity (mV). The symbols (A) to (E) in Fig. 2 are the same as those in Fig. 1. [Figure 3] This is a proton nuclear magnetic resonance spectrum of the sodium salt of the impurity peak (E) shown in Figure 1, where the horizontal axis represents the chemical shift (ppm), the integers near each peak represent the type of carbon represented as a number in the chemical structural formula of sodium 2-bromo-4-(2-bromoethyl)benzenesulfonate shown in the figure, and the numbers to two decimal places near each peak represent the integral ratio of the protons bonded to the carbon. [Figure 4] This is a TOF-MS spectrum of the impurity peak (E) shown in Figure 1, where the horizontal axis represents the mass-to-charge ratio m / z (m represents molecular mass, z represents charge number), and the vertical axis represents signal intensity. The figure in the middle left of Figure 4 shows the mass-to-charge ratio, estimated elemental composition, estimated structure, and desorbed ion species obtained by mass spectrometry, and the figure in the middle right of Figure 4 is an enlarged view of the TOF-MS spectrum. [Figure 5] This is an enlarged HPLC chart of high-purity sodium styrenesulfonate prepared using BEBS synthesized by a conventional method, as described in Comparative Example 8. The horizontal axis represents elution time (minutes), and the vertical axis represents peak intensity (mV). The peaks or arrows shown in the chart indicate (a) sodium orthostyrenesulfonate, (b) sodium 4-(2-bromoethyl)benzenesulfonate, (c) sodium metastyrenesulfonate, (d) sodium bromostyrenesulfonate, and (e) a peak or peak position (presumed) derived from sodium 4-(2-hydroxyethyl)benzenesulfonate. [Figure 6] 6 is an HPLC chart (enlarged view) of high-purity sodium styrenesulfonate prepared using BEBS synthesized by the method of the present invention, as described in Example 12. The horizontal axis represents elution time (minutes) and the vertical axis represents peak intensity (mV). The symbols (a) to (e) in Fig. 6 are the same as those in Fig. 5. DETAILED DESCRIPTION OF THE INVENTION
[0026] The present invention relates to high-purity BEBS in which the content of nuclear brominated BEBS, which may be present as an impurity, is 0.10% or less (where the area % is determined by liquid chromatography (LC) and the peak area % of nuclear brominated BEBS is taken as 100% for the peak area of 4-(2-bromoethyl)benzenesulfonic acid), high-purity styrenesulfonic acids derived from high-purity BEBS and their polymers in which the amount of bound bromine is 400 ppm or less, and their production methods.The present invention was made based on the discovery that by reducing the total bound bromine in styrenesulfonic acids, it is possible to reduce the unstable bound bromine that may be present in styrenesulfonic acids. The "area % determined by liquid chromatography (LC)" refers to the peak area of brominated 2-bromoethylbenzenesulfonic acid expressed as a percentage when 4-(2-bromoethyl)benzenesulfonic acid is measured by liquid chromatography (LC) such as high performance liquid chromatography (HPLC), with the peak area of the target 4-(2-bromoethyl)benzenesulfonic acid taken as 100%. Therefore, "nuclear brominated BEBS is 0.10% or less" means that the peak area of brominated 2-bromoethylbenzenesulfonic acid is 0.10% or less when the peak area of 4-(2-bromoethyl)benzenesulfonic acid is taken as 100%. In other words, the peak area is 1 / 1000 or less of that of 4-(2-bromoethyl)benzenesulfonic acid.
[0027] The reduction in the amount of unstable bound bromine in the above-mentioned bound bromine was confirmed by introducing styrene sulfonic acids into an aqueous polystyrene sulfonic acid solution and tracking the change in the bromine ion concentration, as described above.
[0028] 4-(2-Bromoethyl)benzenesulfonic acid (BEBS) First, the method for producing BEBS with reduced nuclear brominated BEBS of the present invention will be described. The basic process for producing BEBS is the same as in the past, which is the sulfonation of 2-bromoethylbenzene (see, for example, Japanese Patent Publication No. 55-21030), and 2-bromoethylbenzene is produced by the bromination of styrene (see, for example, Japanese Patent Publication No. 6-172232). Specifically, as shown in the reaction scheme below, styrene is dissolved in a hydrocarbon such as hexane or a halogenated hydrocarbon such as perchloroethylene. Hydrogen bromide gas is then added to the styrene while irradiating it with ultraviolet light or while adding a trace amount of a radical generator such as an azo compound, causing anti-Markovnikov addition of hydrogen bromide to the vinyl group of styrene. This reaction yields 2-bromoethylbenzene. Next, in an acid-resistant, dry reactor, 2-bromoethylbenzene is sulfonated using a sulfonating agent such as sulfuric anhydride (sulfur trioxide), fuming sulfuric acid, concentrated sulfuric acid, or chlorosulfuric acid to yield 4-(2-bromoethyl)benzenesulfonic acid.
[0029] [ka]
[0030] The present invention is characterized by the following points (i) to (iv) and differs from conventional methods. (i) 2-bromoethylbenzene and hydrogen bromide that may be present in the reaction solvent are controlled to 100 ppm or less each. (ii) The iron content in 2-bromoethylbenzene and the reaction solvent is controlled to 5 ppm or less. (iii) The water content of 2-bromoethylbenzene and the reaction solvent is controlled to 1000 ppm or less. (iv) The concentration of the sulfonating agent fed to the reactor and the molar ratio of the sulfonating agent to 2-bromoethylbenzene are controlled within specific ranges. If these conditions are not met, the nuclear brominated compound may be easily produced as a by-product, and as a result, the amount of bound bromine in the styrene sulfonic acid compound derived from the nuclear brominated compound increases.
[0031] The hydrogen bromide sometimes present in 2-bromoethylbenzene is believed to be unreacted hydrogen bromide from the raw material. It can be controlled to 100 ppm or less by heating 2-bromoethylbenzene, heating under reduced pressure, bubbling with an inert gas, washing with purified water, weakly alkaline water, or saline, and / or by distillation along with unreacted styrene and the reaction solvent. It is generally unlikely that fresh reaction solvents, such as reagents, contain hydrogen bromide. However, in practical production at chemical plants and other facilities where the target product is produced, unreacted raw materials and reaction solvents are reused (recycled), and hydrogen bromide may be present in these materials. Therefore, when recycled raw materials and reaction solvents are used, the hydrogen bromide content is analyzed and controlled to 100 ppm or less using the same method as above.
[0032] Iron may be present in the reaction system, possibly iron(III) bromide resulting from the hydrogen bromide and water in the reaction system, as described above, but its structure is unknown. The iron content can be controlled to 5 ppm or less, preferably 1 ppm or less, by washing with 2-bromoethylbenzene or the reaction solvent, purifying by distillation, and / or treating with a cation exchange resin (e.g., Amberlite (registered trademark) from Organo Corporation), a chelating fiber (e.g., Chelest Fiber (registered trademark) from Chelest Corporation), a cation exchange filter (e.g., Clangraft from Kitz Microfilter Co., Ltd.), or activated carbon (e.g., Seitz AKSJ (registered trademark) from Osaka Gas Chemicals Co., Ltd.).
[0033] Furthermore, the moisture that may be contained in 2-bromoethylbenzene and the reaction solvent originates from the reaction solvent used for washing 2-bromoethylbenzene with water or for recycling. This moisture has a particularly strong effect on the by-production of brominated BEBS, so it is controlled to 1000 ppm or less, preferably 500 ppm or less, each by distillation and / or using a desiccant. Examples of desiccants include silica gel, zeolite, molecular sieves, calcium chloride, magnesium sulfate, calcium sulfate, sodium sulfate, calcium hydride, phosphorus pentoxide, and alumina. By treating 2-bromoethylbenzene and the reaction solvent with these, the water content in the reaction system can be reduced.
[0034] The BEBS obtained by the above method is usually extracted from the reaction solution with water, and then the reaction solvent and water that were mixed in are distilled off and concentrated to form a 65% to 75% by weight BEBS aqueous solution, which is then used to produce alkali metal styrenesulfonate. The organic solvent used in the sulfonation step of 2-bromoethylbenzene and unreacted 2-bromoethylbenzene are usually recovered and recycled. Since water tends to remain in the recovered organic solvent, it is extremely important to control the water content using the method described above.
[0035] The reaction solvent is not particularly limited as long as it is inert to the sulfonating agent. For example, halogenated solvents such as carbon tetrachloride, 1,2-dichloroethane, methylene chloride, 1,1,2-trichloroethane, chloroform, chlorobenzene, dichlorobenzene, bromobenzene, dibromobenzene, and bromohexane; nitrated solvents such as nitromethane and nitrobenzene; and aliphatic hydrocarbons such as hexane, cyclohexane, and methylcyclohexane can be used.
[0036] In addition to the above, it is also important to control the concentration of the sulfonating agent supplied to the reactor and the molar ratio of the sulfonating agent to 2-bromoethylbenzene within a specific range. From the viewpoint of suppressing the by-production of brominated BEBS, it is preferable that the iron, hydrogen bromide, and water contents in the reaction system be zero or as close to zero as possible. Furthermore, the lower the substrate concentration, especially the sulfonating agent concentration, the better. However, considering practical productivity, there is a limit to how low the substrate concentration can be. To produce high-purity BEBS without sacrificing productivity, it is preferable to react 2-bromoethylbenzene (or its organic solvent solution) and the sulfonating agent (or its organic solvent solution) while simultaneously and continuously supplying them to the reactor. This can be done by a batch system using a tank reactor or a flow system using a tubular or tubular reactor. For mass production, a flow system is preferred from the viewpoint of production efficiency.
[0037] In the present invention, when sulfuric anhydride, which is the most suitable sulfonating agent, is used, it is preferable to maintain the sulfuric anhydride concentration in the reactor at 5.00% to 20.00% by weight and to maintain the molar ratio of sulfuric anhydride to 2-bromoethylbenzene in the reactor, i.e., the ratio of the number of moles fed to the reactor, at 0.50 to 2.00, while carrying out the reaction at 10°C to 60°C for 0.5 to 5.0 hours. Here, the sulfuric anhydride concentration is calculated as (weight of sulfuric anhydride fed to the reactor / weight of the total reaction solution in the reactor) x 100. In order to achieve both a high reaction conversion rate and a high selectivity, it is more preferable to carry out the reaction at 20°C to 50°C for 0.5 to 3.0 hours while maintaining the sulfuric anhydride concentration in the reactor [(weight of sulfuric anhydride supplied to the reactor / weight of the total reaction liquid in the reactor) × 100] at 10.00 to 20.00% by weight and maintaining the molar ratio of sulfuric anhydride to 2-bromoethylbenzene in the reactor (ratio of the number of moles supplied to the reactor) at 0.95 to 1.50.
[0038] In addition to the method of continuously supplying the above-mentioned raw materials to the reactor simultaneously, another reaction method is to continuously supply sulfuric anhydride (or a solution thereof in an organic solvent) to 2-bromoethylbenzene (or its solution in an organic solvent) and react while maintaining a low sulfuric anhydride concentration in the reaction system. In this case, the sulfuric anhydride concentration in the reactor [(weight of sulfuric anhydride supplied to the reactor / weight of the total reaction solution in the reactor) × 100] is increased over 0.5 to 5 hours to a concentration not exceeding 20.00 wt%, and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene in the reactor (the ratio of the number of moles supplied to the reactor) is increased to a molar ratio not exceeding 2.00, while the reaction is carried out at 10°C to 60°C for 0.5 to 10.0 hours.
[0039] The sulfonating agent is preferably sulfuric anhydride, which has high reactivity, can complete the reaction with an equivalent amount, and does not generate by-products such as hydrochloric acid. Furthermore, during the sulfonation reaction, to prevent the formation of sulfones, it is preferable to add an organic carboxylic acid such as acetic acid or acetic anhydride in an amount of 5 to 10% by weight based on the sulfonating agent, and to prevent localization of the sulfonating agent, the reaction is carried out with sufficient stirring. The appropriate amount of sulfonating agent relative to 2-bromoethylbenzene does not necessarily vary depending on the type of sulfonating agent. However, when sulfuric anhydride, which is most suitable in the present invention, is used, 0.50 to 2.00 equivalents is preferred, and 0.95 to 1.20 equivalents is more preferred in order to achieve both a high conversion rate and a high selectivity (suppression of side reactions). Furthermore, for the purpose of mildening the reactivity of sulfuric anhydride, a compound that forms a complex with sulfuric anhydride, such as a tertiary amine such as triethylamine or pyridine, an aprotic polar solvent such as N,N-dimethylformamide, dioxane or dimethyl sulfoxide, or a phosphate triester such as trimethyl phosphate or triethyl phosphate, may be added in an amount of 0.5 to 1.5 equivalents relative to sulfuric anhydride. Because sulfuric anhydride is extremely reactive, it can react sufficiently even at temperatures below 10°C. However, in consideration of temperature control in actual production, temperatures above 10°C are preferable, and in consideration of reaction selectivity, temperatures below 60°C are preferable.
[0040] The mechanism of nuclear brominated BEBS formation that immediately comes to mind is the electrophilic substitution reaction of the benzene ring with Br2 (see, for example, Volkhard Schauer, Modern Organic Chemistry, pp. 698-700, Kagaku Dojin Co., Ltd., 2000). That is, hydrogen bromide, which may be contained in 2-bromoethylbenzene or recycled solvents, is oxidized to Br2, and the trace amounts of iron present in the reaction system may act as a catalyst to form nuclear brominated BEBS.
[0041] However, after detailed investigation of the reaction conditions, the inventors discovered that although nuclear brominated BEBS is indeed produced in the presence of hydrogen bromide and iron, the water content in the reaction system has a greater impact on the actual production process. In other words, when sulfonating 2-bromoethylbenzene using sulfuric anhydride, it was found that even if the raw material hydrogen bromide and iron were removed, more nuclear brominated BEBS was produced if water was present. The bromine source in this case is thought to be the bromine bonded to the ethyl group of 2-bromoethylbenzene, but the reaction mechanism is unclear. In addition, it is expected that various isomers exist in nuclear brominated BEBS, and by separating and identifying the impurities found in liquid chromatographic analysis of BEBS, it was found that one of the main isomers was 2-bromo-4-(2-bromoethyl)benzenesulfonic acid.When styrenesulfonic acids are produced using BEBS, the more nuclear brominated BEBS there is in BEBS, the more bound bromine and unstable bound bromine there is in styrenesulfonic acids.
[0042] <Styrene sulfonic acids> Next, the styrene sulfonic acids of the present invention will be described. Among styrene sulfonic acids, the method for producing alkali metal styrene sulfonates with reduced bound bromine can be basically the same as known methods, except that high-purity BEBS with a reduced content of nuclear-brominated BEBS is used as the raw material. For example, as described above, sodium styrene sulfonate, lithium styrene sulfonate, or potassium styrene sulfonate can be produced by crystallizing BEBS in an aqueous solution while reacting it with an alkali such as sodium hydroxide, lithium hydroxide, or potassium hydroxide (e.g., International Publication No. WO 2014 / 061357 and JP 2015-164911 A).
[0043] The method for producing styrenesulfonic acid esters with reduced bound bromine among styrenesulfonic acids is basically the same as the method described above, except that high-purity BEBS with a reduced content of nuclear brominated BEBS is used as the raw material. That is, sodium styrenesulfonate is reacted with thionyl chloride to produce styrenesulfonyl chloride, which is then esterified with a base such as potassium hydroxide and an alcohol.
[0044] Among styrene sulfonic acids, styrene sulfonyl imide, for example, 4-styrene sulfonyl (trifluoromethyl sulfonyl imide) sodium salt with reduced bound bromine can be produced by essentially the same method as known methods, except that high-purity BEBS with a reduced content of brominated BEBS is used as the raw material (precursor). For example, a method of reacting sodium carbonate, trifluoromethanesulfonamide, and the above-mentioned styrene sulfonyl chloride in an organic solvent can be applied (e.g., JP 2017-132728 A). Furthermore, 4-styrene sulfonyl (fluorosulfonylimide) potassium salt can be produced by, for example, mixing styrene sulfonyl chloride, dipotassium hydrogen phosphate, 4-tert-butylcatechol, and dimethylaminopyridine in acetonitrile at 0°C under a nitrogen atmosphere, adding fluorosulfonamide, and allowing the mixture to react at room temperature for 72 hours. Furthermore, by reacting the potassium salt with lithium perchlorate, it can be derived into 4-styrenesulfonyl(fluorosulfonylimide) lithium salt (e.g., Qiang Ma et al.; RSC Advances, 2016, No. 6, pp. 32454-32461). Furthermore, among bis(styrylsulfonylimide) salts, for example, the lithium salt can be produced by reacting styrenesulfonyl chloride with styrenesulfonylamide in an anhydrous organic solvent in the presence of lithium hydride (e.g., JP 2016-128562 A).
[0045] A method for producing a styrenesulfonic acid amine salt having reduced bound bromine, among styrenesulfonic acids, can be basically the same as a known method except that an alkali metal styrenesulfonate having reduced bound bromine is used as a raw material. For example, a method can be applied in which an aqueous solution of N,N'-dimethylcyclohexylamine hydrochloride is added to an aqueous solution of sodium styrenesulfonate to perform cation exchange, and then the styrenesulfonic acid N,N'-dimethylcyclohexylamine salt is extracted with an organic solvent such as chloroform and dried (e.g., International Publication No. WO2019 / 031454). Among styrene sulfonic acids, the method for producing ammonium styrene sulfonate with reduced bound bromine can be basically the same as known methods, except that an alkali metal styrene sulfonate with reduced bound bromine is used as a raw material. For example, when sodium styrene sulfonate and ammonium sulfate are mixed in methanol at 65°C, ammonium styrene sulfonate soluble in methanol is produced. After filtering off the sodium styrene sulfonate that is insoluble in methanol, ammonium styrene sulfonate can be produced by distilling off the methanol (for example, JP 50-149642 A). Among styrene sulfonic acids, a method for producing phosphonium styrene sulfonate having reduced bound bromine can basically be applied to known methods except for using an alkali metal styrene sulfonate having reduced bound bromine as a raw material. For example, tetrabutylphosphonium styrene sulfonate can be produced by adding tetrabutylphosphonium bromide and sodium styrene sulfonate to water, thoroughly stirring and dissolving, extracting with an organic solvent, and washing with pure water (e.g., International Publication No. WO2015 / 147749).
[0046] <Polystyrene sulfonic acids> In the method for producing polystyrene sulfonic acids of the present invention, styrene sulfonic acids having reduced bound bromine can be used as monomers. Known methods can also be applied to specific production steps. That is, general radical polymerization methods using radical polymerization initiators, photosensitizers, ultraviolet rays, and radiation, and emulsion polymerization methods (e.g., Kamachi et al.; New Edition Radical Polymerization Handbook, 2010, NTS Publishing Co., Ltd.; Lovel Peter A. et al.; Emulsion Polymerization and Emulsion Polymers, 1997, John Wiley & Sons, Ltd.) In addition to the conventional polymerization methods (published by Yahoo! Inc.), controlled radical polymerization methods such as atom transfer polymerization (ATRP), reversible addition-fragmentation transfer (RAFT) polymerization, iodine transfer polymerization (ITP), stable nitroxyl-mediated polymerization (NMP), and organotellurium-mediated polymerization (TERP) can be applied (for example, Yamako et al., Journal of the Society of Rubber Science and Technology of Japan, Vol. 82, No. 8, pp. 363-369, 2009; Uegai et al., Network Polymer, Vol. 30, No. 5, pp. 234-249, 2009). In addition, when using styrene sulfonate esters of styrene sulfonic acids, anionic polymerization using an organometallic catalyst (for example, Tadaki et al., Network Polymer, Vol. 38, No. 1, pp. 14-20, 2017) can also be applied.
[0047] Of the polymerization methods mentioned above, the radical polymerization method, which is highly versatile, will be described in detail. For example, a solvent, styrene sulfonic acids, and, if necessary, a monomer other than styrene sulfonic acids that is radically copolymerizable with styrene sulfonic acids are added to a reaction vessel. A polymerization inhibitor such as the above-mentioned stable nitroxyl compound, a molecular weight regulator such as a mercaptan compound, and a radical polymerization initiator such as an azo compound are then added. After deoxidizing the reaction system, polymerization is carried out while heating to a predetermined temperature, producing a solvent-soluble polymer with the desired molecular weight. The molecular weight of the polymer is 500 to 5,000,000 daltons as a number average molecular weight. However, considering the polymerizability of styrene sulfonic acids, a molecular weight of 500 to 1,000,000 daltons is preferred, and a molecular weight of 1,000 to 600,000 daltons is more preferred.
[0048] Furthermore, among styrene sulfonic acids, styrene sulfonate esters, amine styrene sulfonates, and lithium styrene sulfonates are highly soluble in various solvents, allowing the preparation of highly concentrated solutions. Therefore, for example, a monomer solution containing these styrene sulfonic acids and a photopolymerization initiator, a photosensitizer, a crosslinkable monomer such as divinylbenzene, and optionally a molecular weight regulator or thickener can be injected between transparent glass plates or films, or impregnated into nonwoven fabric, and polymerized by irradiation with ultraviolet light, etc., to easily produce coatings or crosslinked films of polystyrene sulfonic acids. However, in the case of crosslinked films, the polymer is insoluble in solvents, making it difficult to measure the number average molecular weight.
[0049] The solvent used in the reaction is not particularly limited as long as it can dissolve the monomer mixture, and examples thereof include anisole, dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, N,N-dimethylacetamide, dihydrolevoglucosenone, acetonitrile, dioxane, tetrahydrofuran, toluene, benzene, chlorobenzene, xylene, diethyl carbonate, dimethyl carbonate, ethylene carbonate, acetone, methanol, ethanol, propanol, butanol, methoxyethanol, methoxypropanol, propylene glycol monomethyl ether acetate, water, an aqueous solution of an alkali metal halide salt, and a mixed solvent thereof. The amount of the polymerization solvent used is usually 0 to 2,000 parts by weight relative to 100 parts by weight of the total amount of monomers. When a powdery monomer such as styrene sulfonate is polymerized, usually 50 to 1,000 parts by weight of the polymerization solvent is used.
[0050] On the other hand, among styrene sulfonic acids, styrene sulfonate esters and certain amine salts are liquid or low-melting point monomers, so a reaction solvent is not necessarily required. Furthermore, among styrene sulfonic acids, styrene sulfonate esters are oil-soluble monomers and are miscible with general-purpose monomers such as styrene and (meth)acrylic acid esters, so they can also be used in emulsion polymerization, suspension polymerization, or dispersion polymerization. For example, polystyrene sulfonate ester microparticles or microparticles modified with styrene sulfonate ester structural units can be produced by emulsifying or finely dispersing styrene sulfonate ester and a monomer copolymerizable therewith in water using a nonionic emulsifier, anionic emulsifier, cationic emulsifier, and / or water-soluble polymer, followed by polymerization with the addition of a radical polymerization initiator.
[0051] The molecular weight regulator is not particularly limited, and examples thereof include disulfides such as diisopropyl xanthogen disulfide, diethyl xanthogen disulfide, diethylthiuram disulfide, 2,2'-dithiodipropionic acid, 3,3'-dithiodipropionic acid, 4,4'-dithiodibutanoic acid, and 2,2'-dithiobisbenzoic acid, n-dodecyl mercaptan, octyl mercaptan, t-butyl mercaptan, and thio Glycolic acid, thiomalic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiosalicylic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, thiomalonic acid, dithiosuccinic acid, thiomaleic acid, thiomaleic anhydride, dithiomaleic acid, thioglutaric acid, cysteine, homocysteine, 5-mercaptotetrazoleacetic acid, 3-mercapto-1-propanesulfonic acid, 3-mercaptopropane mercaptans such as 1,2-diol, mercaptoethanol, 1,2-dimethylmercaptoethane, 2-mercaptoethylamine hydrochloride, 6-mercapto-1-hexanol, 2-mercapto-1-imidazole, 3-mercapto-1,2,4-triazole, cysteine, N-acylcysteine, glutathione, N-butylaminoethanethiol, and N,N-diethylaminoethanethiol; iodinated hydrocarbons such as iodoform; benzyl dithiobenzoate, 2-cyanoprop-2-yldithiobenzoate, diphenylethylene, p-chlorodiphenylethylene, p-cyanodiphenylethylene, α-methylstyrene dimer, organic tellurium compounds, sulfur, sodium sulfite, potassium sulfite, sodium bisulfite, potassium bisulfite, sodium pyrosulfite, potassium pyrosulfite, and sodium hypophosphite. The amount of molecular weight modifier used is typically 0.0 to 15.0 parts by weight per 100 parts by weight of the total amount of monomers. Molecular weight modifiers are effective additives for reducing the molecular weight and branching of the polymer being produced, or for improving the homogeneity of the membrane when producing a polymer electrolyte using a crosslinkable monomer. However, they can also cause a decrease in polymerization rate and copolymerization, or an odor. Therefore, depending on the purpose, molecular weight modifiers are not necessarily required. Instead, the molecular weight can be adjusted by increasing the amount of polymerization initiator, adjusting the polymerization temperature, or by adjusting the addition conditions of the monomer and polymerization initiator.
[0052] Examples of the radical polymerization initiator include di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, benzoyl peroxide, dilauryl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)-cyclohexane, cyclohexanone peroxide, t-butyl peroxybenzoate, t-butylperoxyisobutyrate, t-butyl Peroxides such as t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisopropyl carbonate, cumylperoxyoctoate, potassium persulfate, ammonium persulfate, and hydrogen peroxide, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(2-methylbutyronitrile), and 1,1'-azobis(2-methylbutyronitrile). Azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano-1-methylethyl)azo]formamide, dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis{2-methyl-N-[1,1'-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis{2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methyl-N-[1,1'-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, Azo compounds such as 2,2'-azobis{2-(2-imidazolin-2-yl)propane]disulfate dihydrate, 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl)propane]}dihydrochloride, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane)dihydrochloride, 2,2'-azobis(2-methylpropionamidine)dihydrochloride, and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]tetrahydrate, 4,4'-Bis(diethylamino)benzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, ethyl-4-(dimethylamino)-benzoate, [4-(methylphenylthio)phenyl]-phenylmethane, ethylhexyl-4-dimethylaminobenzoate, benzophenone, methyl-o-benzoylbenzoate, o-benzoylbenzoic acid, 4-methylbenzophenone, 1-hydroxycyclohexyl phenyl ketone, methylbenzoyl formate, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,2-dimethoxy-2-phenyl Examples of photopolymerization initiators include acetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propane, etc. Furthermore, if necessary, reducing agents such as ascorbic acid, erythorbic acid, aniline, tertiary amines, Rongalite, hydrosulfite, sodium sulfite, and sodium thiosulfate may be used in combination. The amount of the radical polymerization initiator used is usually 0.1 to 15 parts by weight based on 100 parts by weight of the total amount of monomers.
[0053] The polymerization conditions are not particularly limited, but may be heating in an inert gas atmosphere at 20 to 120°C for 4 to 50 hours, and may be adjusted appropriately depending on the polymerization solvent, monomer composition, and type of polymerization initiator. In the case of photopolymerization, the wavelength is 250 to 450 nm, and the illuminance is 20 mW / cm. 2 ~1,000mW / cm 2 The polymerization can be carried out by irradiating the resin with ultraviolet light at 10°C to 60°C for 0.1 to 5 hours.
[0054] The monomer other than styrene sulfonic acids used in the production of the polystyrene sulfonic acids of the present invention is not particularly limited as long as it can be copolymerized with styrene sulfonic acids. For example, styrenes such as styrene, chlorostyrene, dichlorostyrene, bromostyrene, dibromostyrene, fluorostyrene, trifluorostyrene, nitrostyrene, cyanostyrene, α-methylstyrene, p-chloromethylstyrene, p-acetoxystyrene, p-styrenesulfonyl chloride, styrenesulfonyl bromide, styrenesulfonyl fluoride, p-butoxystyrene, 4-vinylbenzoic acid, 3-isopropenyl-α,α'-dimethylbenzyl isocyanate, and vinylbenzyltrimethylammonium chloride; vinyl ethers such as butyl vinyl ether, propyl vinyl ether, ethyl vinyl ether, 2-phenyl vinyl alkyl ether, nitrophenyl vinyl ether, cyanophenyl vinyl ether, chlorophenyl vinyl ether, and chloroethyl vinyl ether; methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate; Pentyl acrylate, hexyl acrylate, decyl acrylate, lauryl acrylate, octyl acrylate, dodecyl acrylate, stearyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, bornyl acrylate, 2-ethoxyethyl acrylate, 2-butoxyethyl acrylate, 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, methoxyethylene glycol acrylate, ethyl carbitol acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 3-(trimethoxysilyl)propyl acrylate, polyethylene glycol acrylate, glycidyl acrylate, 2-(acryloyloxy)ethyl phosphate, 2,2,3,3-tetrafluoropropyl acrylate, 2,2,2-trifluoroethyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,4,4,Acrylic esters such as 4-hexafluorobutyl, methyl methacrylate, t-butyl methacrylate, sec-butyl methacrylate, i-butyl methacrylate, i-propyl methacrylate, decyl methacrylate, lauryl methacrylate, octyl methacrylate, dodecyl methacrylate, stearyl methacrylate, cyclohexyl methacrylate, bornyl methacrylate, benzyl methacrylate, phenyl methacrylate, glycidyl methacrylate, polyethylene glycol methacrylate Acrylate, 2-hydroxyethyl methacrylate, tetrahydrofurfuryl methacrylate, methoxyethylene glycol methacrylate, ethyl carbitol methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 2-(methacryloyloxy)ethyl phosphate, 2-(dimethylamino)ethyl methacrylate, 2-(diethylamino)ethyl methacrylate, 3-(dimethylamino)propyl methacrylate, 2-(isocyanate) methacrylate methacrylate esters such as ethyl methacrylate, 2,4,6-tribromophenyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, 2,2,3,4,4,4-hexafluorobutyl methacrylate, diacetone methacrylate, methacryloxypropyltrimethoxysilane, methacryloxypropyldimethoxysilane, isoprene sulfonic acid, 1,3 -butadiene, 2-methyl-1,3-butadiene, 2-chloro-1,3-butadiene, 2,3-dichloro-1,3-butadiene, 2-cyano-1,3-butadiene, 1-chloro-1,3-butadiene, 2-(N-piperidylmethyl)-1,3-butadiene, 2-triethoxymethyl-1,3-butadiene, 2-(N,N-dimethylamino)-1,3-butadiene, N-(2-methylene-3-butenoyl)morpholine, 2-methylene-3-butenylphosphonic acid diethyl ester, etc.3-Butadienes, N-phenylmaleimide, N-(chlorophenyl)maleimide, N-(methylphenyl)maleimide, N-(isopropylphenyl)maleimide, N-(sulfophenyl)maleimide, N-methylphenylmaleimide, N-bromophenylmaleimide, N-naphthylmaleimide, N-hydroxyphenylmaleimide, N-methoxyphenylmaleimide, N-carboxyphenylmaleimide, N-(nitrophenyl)maleimide, N-benzylmaleimide, N -(4-Acetoxy-1-naphthyl)maleimide, N-(4-oxy-1-naphthyl)maleimide, N-(3-fluoranthyl)maleimide, N-(5-fluoresceinyl)maleimide, N-(1-pyrenyl)maleimide, N-(2,3-xylyl)maleimide, N-(2,4-xylyl)maleimide, N-(2,6-xylyl)maleimide, N-(aminophenyl)maleimide, N-(tribromophenyl)maleimide, N-[4-(2-benzimidazolyl)phenyl]maleimide Maleimides such as imide, N-(3,5-dinitrophenyl)maleimide, N-(9-acridinyl)maleimide, maleimide, N-(sulfophenyl)maleimide, N-cyclohexylmaleimide, N-methylmaleimide, N-ethylmaleimide, and N-methoxyphenylmaleimide; fumaric acid diesters such as dibutyl fumarate, dipropyl fumarate, diethyl fumarate, and dicyclohexyl fumarate; fumaric acids such as butyl fumarate, propyl fumarate, and ethyl fumarate. Monoesters, maleic acid diesters such as dibutyl maleate, dipropyl maleate, and diethyl maleate, maleic acid monoesters such as butyl maleate, propyl maleate, ethyl maleate, and dicyclohexyl maleate, acid anhydrides such as maleic anhydride and citraconic anhydride, acrylamide, N-methylacrylamide, N-ethylacrylamide, 2-hydroxyethylacrylamide, N,N-diethylacrylamide, acryloylmorpholine, N,Acrylamides such as N-dimethylaminopropylacrylamide, isopropylacrylamide, N-methylolacrylamide, sulfophenylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, 2-acrylamido-1-methylsulfonic acid, diacetoneacrylamide, and acrylamidoalkyltrialkylammonium chloride, methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, 2-hydroxyethylmethacrylamide, N,N-diethylmethacrylamide, N,N-dimethylmethacrylamide, N-methylolmethacrylamide, methacryloylmorpholine, N,Methacrylamides such as N-dimethylaminopropyl methacrylamide, isopropyl methacrylamide, 2-methacrylamido-2-methylpropanesulfonic acid, and methacrylamide alkyltrialkylammonium chloride, as well as vinylpyridine, vinyl chloride, vinylidene chloride, vinylpyrrolidone, sulfophenyl itaconimide, acrylonitrile, methacrylonitrile, fumaronitrile, α-cyanoethyl acrylate, citraconic acid, vinyl acetate, vinyl propionate, vinyl pivalate, vinyl versamate, crotonic acid, itaconic acid, fumaric acid, maleic acid, Examples of the acrylic acid include mono-2-(methacryloyloxy)ethyl phthalate, mono-2-(methacryloyloxy)ethyl succinate, mono-2-(acryloyloxy)ethyl succinate, acrolein, vinyl methyl ketone, N-vinyl acetamide, N-vinyl formamide, vinyl ethyl ketone, vinyl sulfonic acid, allyl sulfonic acid, dehydroalanine, sulfur dioxide, isobutene, N-vinyl carbazole, vinylidene dicyanide, paraquinodimethane, chlorotrifluoroethylene, tetrafluoroethylene, norbornene, N-vinyl carbazole, acrylic acid, and methacrylic acid. Among these, (meth)acrylic acid, (meth)acrylic acid esters, N-substituted maleimides, (meth)acrylamides, styrenes, and vinylpyridines are preferred in consideration of copolymerizability with styrene sulfonic acids and availability. Furthermore, the monomers used in producing the crosslinked film or crosslinked particles are not particularly limited, and examples thereof include substituted styrenes such as divinylbenzene, bis-(4-styrenesulfonyl)imide, and divinylbenzenesulfonic acid; (meth)acrylic acid esters such as polyethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, and triethylene glycol diacrylate; N,N'-methylenebisacrylamide, N-[tris(3-acrylamidopropoxymethyl)-methyl]acrylamide, N,N-bis(2-acrylamidoethyl)acrylamide, N,N'-[oxybis(1,2-ethanediyloxy-3,Examples of (meth)acrylamides include N,N'-1,2-ethanediylbis{N-[2-(acryloylamino)ethyl]acrylamide}, N,N'-methylenebismethacrylamide, and other (meth)acrylamides; and substituted maleimides such as 1,2-bismaleimidoethane, 4,4'-bismaleimidodiphenylmethane, 1,6-bismaleimidohexane, 1,4-bismaleimidobutane, N,N'-1,4-phenylenedimaleimide, and N,N'-1,3-phenylenedimaleimide. The proportion of the monomer copolymerizable with the styrene sulfonic acids to be used is 0.0 mol % to 99.0 mol % of the total monomers. For example, when polystyrene sulfonic acids are used as a dopant for a conductive polymer dispersion, the proportion of the monomer is 0.0 mol % to 50.0 mol %, because a smaller amount is better in terms of dispersion stability and conductivity, but a larger amount is better in terms of water resistance and durability of the conductive film. Furthermore, when used in a polymer electrolyte membrane, the concentration of the sulfonic acid group determines the performance such as ion exchange capacity, so the amount of the monomer used is limited, for example, to 0.0 mol % to 30 mol %. On the other hand, for example, when polystyrene sulfonic acids are used as spacer fine particles for liquid crystal displays, the monomer is the main component, and the styrene sulfonic acids are stabilizers for producing the fine particles, i.e., minor components (secondary components), and therefore the content is 50.0 mol% to 99.0 mol%. The copolymerization method is not particularly limited, and in addition to random copolymers, alternating copolymers and graft copolymers, block copolymers can also be produced by applying the above-mentioned controlled polymerization method.
[0055] The BEBS with reduced nuclear bromination produced by the present invention is extremely useful as a precursor for producing styrene sulfonic acids and their polymers with reduced bound bromine. The polymers of styrene sulfonic acids can be used as is, but the bound bromine can be further reduced by subjecting them to the following chemical treatment. That is, in this method, an alkali, or an alkali and a reducing agent, is added to the aqueous solution of polystyrene sulfonic acids obtained above, and the solution is heated at 80°C to 150°C for 5 to 30 hours while maintaining the pH of the solution at 13 or higher to liberate the bound bromine present in the polymer, and then the polymer is purified. To reduce the bound bromine without causing degradation of the polymer, such as coloration, heat treatment at 90°C to 110°C for 10 to 25 hours is more preferred.
[0056] The chemical treatment may be carried out in air, but an inert gas atmosphere such as nitrogen or argon is preferred from the viewpoint of preventing deactivation of the reducing agent and deterioration of the polystyrene sulfonic acids. Examples of alkalis include sodium hydroxide, potassium hydroxide, lithium hydroxide, tetramethylammonium hydroxide, and tetraethylammonium hydroxide. Examples of reducing agents include sodium sulfite, Rongalite, hydrosulfite, sodium thiosulfate, and sodium hypophosphite. The amount of reducing agent added is 0.5 to 1.5 times the molar amount of the alkali. Another chemical treatment method is to combine a reducing agent such as sodium formate or hydrazine with a palladium carbon catalyst. For example, 1.0 to 5.0% by weight of the reducing agent and 1.0 to 20% by weight of palladium carbon (when the Pd content is 5% by weight) are added to the pure content of polystyrene sulfonic acids, and the mixture is treated at 80 to 110°C for 5 to 30 hours.
[0057] As a purification method after treatment, methods using a cation exchange resin, an anion exchange resin, a cation exchange filter, an anion exchange filter, a chelating fiber, an ultrafiltration membrane and activated carbon, reprecipitation purification, etc. can be applied, but in consideration of applicability to a highly viscous aqueous polymer solution, the use of a cation exchange resin, an anion exchange resin and an ultrafiltration membrane is preferred.
[0058] The polystyrene sulfonic acid aqueous solution of the present invention can be used for various applications as is, but to prevent polymer chain scission during long-term storage, it is preferable to add a phenolic antioxidant as a stabilizer in an amount of 20 ppm to 2,000 ppm relative to the pure polystyrene sulfonic acid content. The phenolic antioxidant is not particularly limited, but is preferably one that dissolves in the polystyrene sulfonic acid aqueous solution, such as 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 4-tert-butylcatechol, hydroquinone, methoxyhydroquinone, or ethoxyhydroquinone.
[0059] Furthermore, when the polystyrene sulfonic acid of the present invention is neutralized with ammonia, an amine, tetramethylammonium hydroxide, tetraethylammonium hydroxide, or the like and used as an ammonium salt, that is, when the pH of the aqueous solution is neutral or higher, the addition of the antioxidant is not necessarily required.
[0060] The styrene sulfonic acids and polymers thereof of the present invention with reduced bound bromine have reduced unstable bound bromine that would be liberated under mild conditions, and are therefore extremely useful, particularly in electronic material applications such as battery components, organic EL components, photoresist components, dispersants and dopants for conductive polymers and carbon nanotubes, dispersants for chemical mechanical polishing slurries, and semiconductor cleaning agents. [Example]
[0061] The present invention will be explained in more detail with reference to the following examples, but the present invention is not limited to these examples in any way.
[0062] In the following examples, analysis and evaluation of compounds were carried out under the following conditions. <Analysis of iron in BEB and organic solvents by inductively coupled plasma atomic emission spectrometry (ICP-AES)> Apparatus: PerkinElmer NexIon (trademark) 300S Sample preparation: Approximately 0.1 g of sample was accurately weighed into a 25 ml polypropylene measuring flask, 1 ml of 68% high-purity nitric acid was added, and the mixture was made up to the measuring volume with ultrapure water to prepare the sample for measurement.
[0063] <Analysis of water content in BEB and organic solvents by Karl Fischer method> Device: Kyoto Electronics Manufacturing Co., Ltd. MKC-610 Anolyte: Chem-Aqua Anolyte AGE (Kyoto Electronics Manufacturing Co., Ltd.) Catholyte: ChemAqua Catholyte CGE (Kyoto Electronics Manufacturing Co., Ltd.)
[0064] <Analysis of hydrogen bromide in BEB and organic solvents by ion chromatography (IC)> Equipment: Tosoh Corporation IC-2001 Column: TSKgel (registered trademark) SuperIC-AP Detector: Electrical conductivity, Flow rate: 0.8 ml / min, Column temperature: 40°C Calibration curve: Absolute calibration curve method using anion standard solutions Sample preparation: The sample was extracted by shaking with ultrapure water, then centrifuged, and the aqueous layer was passed through a pretreatment cartridge (TOYOPAK (registered trademark) ODS M, manufactured by Tosoh Corporation) to prepare a measurement sample. The dilution ratio was adjusted depending on the HBr concentration, for example, sample / ultrapure water = 2 ml / 200 ml to 2 ml / 4 ml.
[0065] <Measurement of BEB conversion rate by high performance liquid chromatography (HPLC)> The conversion rate (area %) of BEB in the sulfonation reaction of BEB was measured under the following conditions. Equipment: Tosoh Corporation Column: TSKgel (registered trademark) ODS-80™ (4.6 mm I.D. x 25 cm) Eluent: A) 20 mM NaH2PO4 (pH = 2.4) aqueous solution / acetonitrile = 90 / 10 volume ratio B) 20 mM NaH2PO4 (pH = 2.4) aqueous solution / acetonitrile = 60 / 40 volume ratio Gradient: A → B (linear gradient for 60 minutes, followed by B solution for 30 minutes) Detector: UV230m, Column temperature: 25°C, Flow rate: 0.8ml / min, Injection volume: 20μl
[0066] <Analysis of BEBS aqueous solution concentration by high performance liquid chromatography (HPLC)> The concentration of the BEBS aqueous solution was analyzed under the following conditions. Column: TSKgel® ODS-80TsQA (4.6 mm I.D. x 25 cm) Eluent: Water / acetonitrile = 80 / 20 volume ratio + 0.1 wt% trifluoroacetic acid Detector: UV230m Column temperature: 40°C, flow rate: 0.8 ml / min Calibration curve: Absolute calibration curve method using crystals recovered from the BEBS aqueous solution prepared in Example 2 as a standard substance
[0067] <Analysis of impurities in BEBS by high performance liquid chromatography (HPLC)> The nuclear brominated compounds (area %) in the BEBS aqueous solution were analyzed under the following conditions. Equipment: Tosoh Corporation Column: TSKgel (registered trademark) ODS-80™ (4.6 mm I.D. x 25 cm) Eluent: A) 20 mM NaH2PO4 (pH = 2.4) aqueous solution / acetonitrile = 90 / 10 volume ratio B) 20 mM NaH2PO4 (pH = 2.4) aqueous solution / acetonitrile = 60 / 40 volume ratio Gradient: A → B (linear gradient 60 min) Detector: UV230m, Column temperature: 25°C, Flow rate: 0.8ml / min, Injection volume: 20μl Sample preparation: BEBS aqueous solution (concentration 69.0-73.0 wt%) 5 mg / eluent 1 ml
[0068] The UK components in BEBS produced by the conventional method (Comparative Example 4 below), i.e., peaks (A), (C), (D), and (E) in Figure 1, were identified in advance by the following method. Each component was separated by column, and the sulfonic acid groups were methyl-esterified with diazomethane. Then, gas chromatography mass spectrometry (Hitachi M-80B), Fourier transform infrared spectrometry (PerkinElmer System 2000), organic elemental analysis (Yanaco CHN Coder MT-3), and nuclear magnetic resonance spectrometry (Varian VXR-300) were performed to attempt identification. Furthermore, (E) was directly identified by TOF-MS without esterification.
[0069] <Identification of nuclear brominated BEBS by time-of-flight mass spectrometry (TOF-MS)> The TOF-MS of the peak (E) detected by the above HPLC was measured. Instrument: Bruker Daltonics microTOF Ion source: ESI Measurement mode: Negative mode Sample preparation: The sample was dissolved in methanol and then diluted with methanol / water at a volume ratio of 1 / 1.
[0070] <Proton nuclear magnetic resonance spectroscopy ( 1 Analysis of ClSS Toluene Solution Concentration by H-NMR Styrene sulfonyl chloride (ClSS) solution under the following conditions 1 H-NMR was measured. Equipment: Bruker AV-400M Solvent: deuterated dimethyl sulfoxide The ClSS concentration was calculated from the integral ratio of two meta-position protons of toluene to one proton of CH2= in the ClSS vinyl group CH2=CH- using the following formula. ClSS concentration = 100 × 202.65 / (202.65 + 92 × toluene integral ratio / 2)
[0071] <Analysis of ETSS by gas chromatography (GC)> The GC purity (area %) of ethyl styrenesulfonate (ETSS) was analyzed under the following conditions. Equipment: Shimadzu Corporation GC-2014 Column: NEUTRABOND-1 (φ0.32 mm × 30 m, 0.4 μm) Injection: 220℃, injection volume 0.2μl Carrier gas: Helium, Linear velocity: 30 cm / min, Split ratio: 100 Detector: FID, 250℃ Heating conditions: 80°C x 10 minutes, then heat to 250°C at 5°C / min and hold for 6 minutes Sample: Neat
[0072] <Analysis of NaSS by High Performance Liquid Chromatography (HPLC)> Various organic impurities and isomers that may be contained in sodium 4-styrenesulfonate were analyzed under the following conditions, which are the same as those used in a patent document (International Publication No. WO2014 / 061357). Equipment: Tosoh Corporation Column: TSKgel (registered trademark) ODS-80™ (4.6 mm I.D. x 25 cm) Eluent: A) 5 vol% acetonitrile aqueous solution (containing 0.1% trifluoroacetic acid) B) 20 vol% acetonitrile aqueous solution (containing 0.1% trifluoroacetic acid) Gradient: 100% solution A (0-55 min) → 100% solution B (55-95 min) Detector: UV230m, Column temperature: 25°C, Flow rate: 0.8ml / min, Injection volume: 20μl Sample preparation: Dissolve the sample in eluent A to prepare a solution with an apparent concentration of 0.5 mg / 1 ml.
[0073] <Measurement of pure sodium styrene sulfonate> The active double bonds were quantified by oxidation-reduction titration to determine the sodium styrenesulfonate content in the sample (i.e., including the para isomer as well as the ortho and meta isomers). (1) Reagents 1) Bromine solution: 22.00 g of potassium bromide and 3.00 g of potassium bromate were dissolved in pure water to make up a total volume of 1000 ml. 2) Sulfuric acid aqueous solution (concentrated sulfuric acid / pure water volume ratio = 1 / 1) 3) Potassium iodide aqueous solution (200g / L) 4) 0.1 mol / L sodium thiosulfate aqueous solution 5) Starch aqueous solution: 6.00 g of starch was dissolved in pure water to make up a total volume of 1000 ml. (2) Operation 1) Weigh 20 g of sample into a weighing bottle to the nearest 0.1 mg. 2) Rinse with pure water and transfer to a 500 ml measuring flask to bring the volume to approximately 400 ml. 3) Add a magnetic rotor and stir to dissolve the sample. 4) Remove the rotor, align the gauge with pure water, shake and mix to use as the test solution. 5) Add 25 ml of bromine solution to a 500 ml stoppered Erlenmeyer flask containing 200 ml of pure water. 6) After adding 5 ml of the test solution, add 10 ml of aqueous sulfuric acid solution, seal the vial tightly, and leave it for 20 minutes. 7) Quickly add 10 ml of potassium iodide solution and leave for 10 minutes. 8) Titrate with an aqueous sodium thiosulfate solution. After the yellow color of the solution fades, add 1 ml of starch solution as an indicator and titrate until the blue color of the resulting iodine starch disappears. 9) As a separate blank test, add 200 ml of pure water to a stoppered Erlenmeyer flask, add 25 ml of bromine solution, quickly add 10 ml of potassium iodide aqueous solution and 10 ml of sulfuric acid aqueous solution, and repeat procedure 8). (3) Calculation Calculate the sodium styrene sulfonate content using the following formula. A=100×[0.01031×(ab)×f] / (S×5 / 500) A: Sodium styrene sulfonate content (%) a: Sodium thiosulfate aqueous solution required for blank test (ml) b: Sodium thiosulfate solution required for this test (ml) f: Potency of sodium thiosulfate solution S: Sample size (g)
[0074] <Analysis of halogens in styrenesulfonic acids by combustion decomposition ion chromatography> The bromine and chlorine contents in styrene sulfonic acids and polystyrene sulfonic acid were determined under the following conditions. Combustion equipment: Mitsubishi Chemical Analytech AQF-2100H Combustion temperature: inlet=900℃, outlet=1000℃ IC device: Tosoh Corporation IC-2010 Column: TSK-guard column Super IC-AHS + TSK-gel Super IC-Anion HS Eluent: Carbonate buffer Absorbing solution: 900 ppm hydrogen peroxide solution Detector: Electrical conductivity Flow rate: 1.5ml / min, temperature: 40℃ Measurement mode: Suppressor type Calibration curve: Absolute calibration curve method using anion standard solutions
[0075] <Analysis of halogen ions in aqueous polystyrene sulfonic acid solution by ion chromatography> The halogen ions in an aqueous solution of polystyrene sulfonic acid were quantified under the following conditions. Equipment: Tosoh Corporation IC-2001 Column: TSKgel (registered trademark) Super IC-AP Detector: Electrical conductivity Sample preparation: 20 g of sample was diluted with ultrapure water to a concentration of 20 mg / ml, and then polymer components were removed using an ultrafiltration cartridge (molecular weight cutoff of 3,000 or 10,000) to prepare a sample for analysis.
[0076] <Determination of water content in 4-styrenesulfonate> Approximately 2 g of sample was weighed to the nearest 0.1 mg into a weighing bottle (diameter 55 mm x height 30 mm) and dried in a dryer (105 ± 5°C) for 90 minutes. Immediately transferred to a desiccator and cooled to room temperature, the mass was measured to the nearest 0.1 mg and the moisture content was calculated using the following formula. Moisture (wt%)=100×(ab) / S a: Weight of the sample and weighing bottle before drying (g), b: Weight of the sample and weighing bottle after drying (g), S: Sample weight (g)
[0077] <Determination of bromide ions in 4-styrenesulfonic acids> Equipment: Tosoh Corporation, IC-2010 Column: TSKgel® guard column Super IC-AHS (4.6 mm I.D. x 1 cm) + TSKgel Super IC-Anion HS (4.6 mm I.D. x 10 cm) Column temperature: 40°C, injection volume: 30 μl, flow rate: 1.5 ml / min Eluent: Carbonate buffer (7.5mM-NaHCO3 + 0.8mM-Na2CO3) Sample preparation for styrene sulfonate esters: 5 ml of ultrapure water and 5 g of sample were placed in a screw-cap test tube, and after shaking for 30 minutes, the mixture was centrifuged (2800 rpm, 30 minutes). The aqueous layer was passed through a pretreatment cartridge (TOYOPAK ODSM) to prepare the measurement sample. Sample preparation of styrene sulfonates: A solid sample was dissolved in ultrapure water to dilute it 10 times, and the solution was passed through a pretreatment cartridge (TOYOPAK (registered trademark) ODSM) to prepare a measurement sample. Calibration curve: Absolute calibration curve method using standard solutions
[0078] <Analysis of polymerization conversion rate of styrene sulfonate ester and molecular weight of produced polymer by gel permeation chromatography (GPC)> The area-based conversion rate and molecular weight were measured under the following conditions. Model: Tosoh Corporation HLC-8320GPC Column: TSK guard column Super AW-H + TSK Super AW-6000 + TSK Super AW-4000 + TSK Super AW-2500 Eluent: N,N-dimethylformamide (lithium bromide 10 mM) Column temperature: 40°C, flow rate: 0.5 ml / min Detector: RI detector, injection volume: 10 μl Calibration curve: Created from the weight average molecular weight and elution time of standard polystyrene kit PSt Quick C, D, and E manufactured by Tosoh. Conversion rate: The polymerization conversion rate was calculated from the peak area (a) derived from the monomer and the peak area (b) derived from the polymer using the following formula. Conversion rate (area%) = 100 × [1-{a / (a+b)}]
[0079] <Analysis of polymerization conversion rate of styrene sulfonate and molecular weight of produced polymer by gel permeation chromatography (GPC)> The area-based conversion rate and molecular weight were measured under the following conditions. Model: Tosoh Corporation HLC-8320GPC Column: TSK guard column AW-H + TSK AW6000 + TSK AW3000 + TSK AW2500 Eluent: 0.05M sodium sulfate aqueous solution / acetonitrile = 65 / 35 volume ratio Flow rate: 0.6 ml / min, injection volume: 10 μl, column temperature: 40°C Detector: UV detector (wavelength 230 nm) Calibration curve: A calibration curve was prepared using standard sodium polystyrene sulfonate (manufactured by Sowa Scientific) from the peak top molecular weights and elution times of the peak tops (3K, 15K, 41K, 300K, 1000K, 2350K, 5000K). Conversion rate: The polymerization conversion rate was calculated from the peak area (a) derived from the monomer and the peak area (b) derived from the polymer using the following formula. Conversion rate (area%) = 100 × [1-{a / (a+b)}]
[0080] <Medications used> 2-Bromoethylbenzene: Tosoh Finechem Co., Ltd., purity 99.1% 1,2-Dichloroethane: Tosoh Corporation, purity 99.9% Sulfuric anhydride: Nisso Sulfan (registered trademark), manufactured by Nisso Metal Chemical Co., Ltd., purity 99.4% Acetic acid: Tokyo Chemical Industry Co., Ltd. Purity >99.5% Anhydrous barium hydroxide: Fujifilm Wako Pure Chemical Industries, Ltd. Triethyl orthoacetate: Tokyo Chemical Industry Co., Ltd. Purity >96% t-Butylcatechol: Fujifilm Wako Pure Chemical Industries, Ltd., purity 98% Potassium t-butoxide: Tokyo Chemical Industry Co., Ltd. Purity >97% N,N-Dimethylformamide: Tokyo Chemical Industry Co., Ltd., purity >99.5% Irganox 1010: BASF Japan Ltd. Thionyl chloride: Tokyo Chemical Industry Co., Ltd. Purity >98% Neopentyl alcohol: Tokyo Chemical Industry Co., Ltd. Purity >98% Trifluoromethanesulfonamide: Tokyo Chemical Industry Co., Ltd. Purity >98% Pyridine: Tokyo Chemical Industry Co., Ltd. Purity >99% 4-Dimethylaminopyridine: Tokyo Chemical Industry Co., Ltd. Purity >98% Sodium carbonate: Tokyo Chemical Industry Co., Ltd. Purity >99% Ethyl acetate: Tokyo Chemical Industry Co., Ltd. Purity >98% Toluene: Tokyo Chemical Industry Co., Ltd. Purity >99.5% Sodium formate: Fujifilm Wako Pure Chemical Industries, Ltd. Purity >95% Palladium carbon: Fujifilm Wako Pure Chemical Industries, Ltd. Pd content 5 wt%
[0081] <Compound abbreviation> BEB: 2-bromoethylbenzene BEBS: 4-(2-bromoethyl)benzenesulfonic acid NaSS: Sodium 4-styrenesulfonate LiSS: Lithium 4-styrenesulfonate PolyNaSS: Poly(sodium 4-styrenesulfonate) PolyLiSS: Poly(lithium 4-styrenesulfonate) PSS: Poly(4-styrenesulfonic acid) ClSS: 4-styrenesulfonyl chloride ETSS: Ethyl 4-styrenesulfonate PolyETSS: Poly(ethyl 4-styrenesulfonate) NPSS: Neopentyl 4-styrenesulfonate PolyNPSS: Poly(neopentyl 4-styrenesulfonate) TfNS-Na: 4-styrenesulfonyl(trifluoromethylsulfonylimide) sodium PolyTfNS-Na: Poly[4-styrenesulfonyl(trifluoromethylsulfonylimide) sodium] PolyTfNS-H: Poly[4-styrenesulfonyl(trifluoromethylsulfonylimide)] BVBSI-Li: Lithium bis-(4-styrenesulfonyl)imide
[0082] Example 1 Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (1) A 1 L four-neck glass flask equipped with a reflux condenser, nitrogen inlet, thermometer insertion tube, and dropping funnel was charged with 233.80 g (1.25 mol) of 2-bromoethylbenzene (Tosoh Finechem Corporation) and 250.30 g of 1,2-dichloroethane (Tosoh Corporation). The dropping funnel was charged with a mixed solution of 111.30 g (1.38 mol) of sulfuric anhydride, 8.00 g (0.13 mol) of acetic acid, and 250.10 g of 1,2-dichloroethane. The 2-bromoethylbenzene was washed with pure water, treated with cation-exchangeable Chelest Fiber® IRY-LC12 (Chilest Corporation), and then dried over molecular sieves to confirm that it contained less than 1 ppm of iron, 20 ppm of hydrogen bromide, and 20 ppm of water. The 1,2-dichloroethane was dried over molecular sieves and confirmed to have a moisture content of 63 ppm, and iron and hydrogen bromide contents of less than 1 ppm each. Under a nitrogen atmosphere, the mixture was thoroughly stirred with a magnetic stirrer and the internal temperature was controlled at 30-40°C. A mixed solution of sulfuric anhydride and acetic anhydride was added dropwise over one hour. After the dropwise addition, the mixture was aged at 40°C for one hour. The concentration of sulfuric anhydride supplied to the reactor was 0.00-12.96 wt% from the start to the end of the reaction, and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene was 0.00-1.10 (the reaction conversion of 2-bromoethylbenzene after aging was 97.6%).
[0083] After aging, 162.80 g of pure water was added while maintaining the internal temperature at 30-40°C. After thorough stirring, the mixture was allowed to stand, and the lower layer of aqueous solution containing BEBS was recovered using a separatory funnel. The remaining 1,2-dichloroethane and water were removed from the aqueous solution using a rotary evaporator, yielding 437.32 g of a concentrated aqueous BEBS solution. The BEBS concentration measured by HPLC was 70.4 wt%, i.e., the yield based on the amount of 2-bromoethylbenzene added was 92.8%. The BEBS aqueous solution was analyzed by HPLC, and the purity was 96.2% by area. When the peak area of BEBS was taken as 100, the peak area of nuclear brominated BEBS was 0.01%. As shown in Table 1, it is clear that the content of nuclear brominated BEBS is lower than that of Comparative Examples 1 to 7 shown in Table 3. The 2-bromoethylbenzene used was an intermediate product (industrial product) obtained in the manufacturing process of sodium styrenesulfonate (Spinomer (registered trademark) NaSS, manufactured by Tosoh Finechem Corporation).
[0084] Examples 2 to 5 Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (2 to 5) A BEBS aqueous solution was prepared using the same raw materials as in Example 1, except for the initial charge, the composition of the dropping solution, the dropping rate, and the reaction temperature. As shown in Table 1, Example 2 had a lower sulfuric anhydride concentration in the reaction system, resulting in even less nuclear brominated BEBS than Example 1. Example 3 had a higher sulfuric anhydride concentration in the reaction system, and Example 4 had a higher molar ratio of sulfuric anhydride to 2-bromoethylbenzene, resulting in slightly more nuclear brominated BEBS than Example 1. Furthermore, although the reaction temperature was high in Example 5, the sulfuric anhydride concentration was low, which is thought to have resulted in the same level of nuclear brominated BEBS as Example 3. In any case, it is clear that the content of nuclear brominated BEBS was lower than in Comparative Examples 1 to 7 shown in Table 3.
[0085] Examples 6-7 Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (6-7) A BEBS aqueous solution was synthesized in the same manner as in Examples 4 and 5, except that the 1,2-dichloroethane used in the reaction in Examples 1 to 5 was recovered, washed with water, and used as the reaction solvent. As shown in Table 1, the content of nuclear brominated BEBS is higher than in Examples 1 to 5 due to the high water content in 1,2-dichloroethane, but it is clear that it is lower than in Comparative Examples 1, 2, 4, 6, and 7 (Table 3), which have higher water content.
[0086] Examples 8-9 Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (8-9) An aqueous BEBS solution was synthesized in the same manner as in Examples 1 to 5, except that 2-bromoethylbenzene was not washed with water or dried over a molecular sieve. As shown in Table 1, the content of nuclear brominated BEBS is higher than in Examples 1 to 5 due to the high hydrogen bromide content in 2-bromoethylbenzene. However, it is clear that the content is lower than in Comparative Example 3, which contains high amounts of hydrogen bromide and iron, and in Comparative Examples 4 and 7 (Table 3), which contain high amounts of hydrogen bromide, iron, and water. The 2-bromoethylbenzene used was an intermediate product (industrial product) obtained in the manufacturing process of sodium styrenesulfonate (Spinomer (registered trademark) NaSS, manufactured by Tosoh Finechem Corporation).
[0087] [Table 1]
[0088] Example 10 Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (10) A 1-L glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a thermometer insertion tube was charged with 433.50 parts by weight of a 1,2-dichloroethane solution of 2-bromoethylbenzene (a mixed solution of 233.50 parts by weight of 2-bromoethylbenzene and 200.00 parts by weight of 1,2-dichloroethane) per hour, and 419.40 parts by weight of a 1,2-dichloroethane solution of sulfuric anhydride (a mixed solution of 111.40 parts by weight of sulfuric anhydride, 8.00 parts by weight of acetic acid, and 300.00 parts by weight of 1,2-dichloroethane) per hour at a rate of 433.50 parts by weight per hour, while the reaction was carried out at an internal temperature of 40 to 50°C under stirring. The reaction solution was withdrawn intermittently every 10 minutes using a pump, and 852.90 parts by weight was withdrawn per hour. The apparent residence time of the reaction liquid at this time was 1 hour, the sulfuric anhydride concentration in the reactor was 12.98 wt%, the molar ratio of sulfuric anhydride to 2-bromoethylbenzene was 1.11, and the reaction conversion rate of BEB was 98.2%. The 2-bromoethylbenzene and 1,2-dichloroethane used were the same as those used in Examples 1 to 5. To 852.90 parts by weight of the extracted reaction solution, 162.80 parts by weight of pure water was added and thoroughly stirred, and then the lower layer of aqueous solution containing BEBS was recovered. The remaining 1,2-dichloroethane and water were distilled off from the aqueous solution using a rotary evaporator, yielding 438.86 parts by weight of a concentrated BEBS aqueous solution. The BEBS concentration measured by HPLC was 70.4% by weight (yield based on BEB: 93.3%). The BEBS aqueous solution was analyzed by HPLC. As shown in Table 2, the purity of BEBS was 96.8% by area, and the peak area of nuclear brominated BEBS was 0.01% when the peak area of BEBS was taken as 100. It is clear that the content of nuclear brominated BEBS was lower than that of Comparative Examples 1 to 7 shown in Table 3.
[0089] Example 11 Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (11) A 1-L glass flask equipped with a reflux condenser, nitrogen inlet, and thermometer insertion tube was charged with 233.50 parts by weight of 2-bromoethylbenzene and 619.60 parts by weight of a solution of sulfuric anhydride in 1,2-dichloroethane (a mixed solution of 111.60 parts by weight of sulfuric anhydride, 8.00 parts by weight of acetic acid, and 500.00 parts by weight of 1,2-dichloroethane) at a rate of 233.50 parts by weight per hour. The reaction was carried out at an internal temperature of 40-50°C under stirring. The reaction solution was withdrawn intermittently every 10 minutes using a pump, with a rate of 853.10 parts by weight withdrawn per hour. The apparent residence time of the reaction solution was 1 hour. The sulfuric anhydride concentration in the reactor was 13.00 wt%, and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene was 1.11. The reaction conversion of BEB was 97.90%. The 2-bromoethylbenzene and 1,2-dichloroethane used were the same as those used in Examples 1 to 5. To 853.10 parts by weight of the extracted reaction solution, 163.00 parts by weight of pure water was added and thoroughly stirred, and then the lower layer of aqueous solution containing BEBS was recovered. The remaining 1,2-dichloroethane and water were distilled off from the aqueous solution using a rotary evaporator, yielding 440.65 parts by weight of a concentrated BEBS aqueous solution. The BEBS concentration measured by HPLC was 69.90 wt% (yield based on BEB: 93.01%). The BEBS aqueous solution was analyzed by HPLC. As shown in Table 2, the purity of BEBS was 96.3% by area, and the peak area of brominated BEBS was 0.01% when the peak area of BEBS was taken as 100. This is clearly lower than that of Comparative Examples 1 to 7 shown in Table 3.
[0090] [Table 2]
[0091] Comparative Example 1: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (12) A 1 L four-neck glass flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer insertion tube, and a dropping funnel was charged with 233.30 g (1.25 mol) of 2-bromoethylbenzene and 497.70 g of 1,2-dichloroethane. The dropping funnel was charged with a mixed solution of 111.30 g (1.38 mol) of sulfuric anhydride and 8.00 g (0.13 mol) of acetic acid. The 2-bromoethylbenzene was washed with pure water, treated with cation-exchangeable Chelest Fiber (registered trademark) IRY-LC12 (manufactured by Chelest Corporation), and then dried over molecular sieves. It was confirmed that the iron content was less than 1 ppm, the hydrogen bromide content was 20 ppm, and the water content was 69 ppm. The 1,2-dichloroethane used in Examples 10 and 11 was recovered and then washed with water, and the iron content and hydrogen bromide content were each less than 1 ppm, and the water content was 2145 ppm. Under a nitrogen atmosphere, the mixture was thoroughly stirred with a magnetic stirrer and the internal temperature was controlled at 30-40°C while a mixed solution of sulfuric anhydride and acetic anhydride was added dropwise over one hour. After the dropwise addition, the mixture was aged at 40°C for one hour. The concentration of sulfuric anhydride supplied to the reactor was 0.00-13.01 wt% from the start to the end of the reaction, and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene was 0.00-1.11. The reaction conversion of BEB was 96.4%.
[0092] After aging, 163.00 g of pure water was added while maintaining the internal temperature at 30-40°C. After thorough stirring, the mixture was allowed to stand, and the lower layer of aqueous solution containing BEBS was recovered using a separatory funnel. The remaining 1,2-dichloroethane and water were removed from the aqueous solution using a rotary evaporator, yielding 420.30 g of a concentrated BEBS aqueous solution. The BEBS concentration measured by HPLC was 72.1 wt% (yield based on BEB: 91.6%). The BEBS aqueous solution was analyzed by HPLC, and as shown in Table 3, the purity of BEBS was 91.3 area %, and the peak area of the nucleobrominated BEBS was 0.31% when the peak area of BEBS was taken as 100, which is significantly higher than that of Examples 1 to 11 shown in Tables 1 and 2. This is thought to be due to the high water content in the reaction system, which promoted side reactions. The above 2-bromoethylbenzene was prepared by dissolving sodium styrenesulfonate (Tosoh Finechem Co., Ltd., Spinomer NaSS TM The intermediate product (industrial product) obtained in the manufacturing process of
[0093] Comparative Example 2: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (13) A concentrated BEBS aqueous solution was synthesized by the same procedure as in Comparative Example 1, except that recycled 1,2-dichloroethane with a different water content was used as the reaction solvent. As shown in Table 3, it is clear that the content of brominated BEBS increased because the water content in 1,2-dichloroethane was higher than that in Comparative Example 1. This is thought to be because the higher water content in the reaction system further accelerated side reactions.
[0094] Comparative Example 3: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (14) A concentrated aqueous BEBS solution was synthesized using the same procedures as in Examples 4 and 5, except that 2-bromoethylbenzene was used that had not been washed with water, treated with a cation exchange filter, or dried over a molecular sieve. As shown in Table 3, the iron content, hydrogen bromide content, and water content in 2-bromoethylbenzene were higher than in Examples 1 to 11, and therefore the content of brominated BEBS was significantly increased. This is thought to be due to the impurities in the reaction system further promoting side reactions. The 2-bromoethylbenzene used was an intermediate product (industrial product) obtained in the manufacturing process of sodium styrenesulfonate (Spinomer NaSS (registered trademark) manufactured by Tosoh Finechem Corporation).
[0095] Comparative Example 4: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (15) A concentrated BEBS aqueous solution was synthesized using the same procedures as in Comparative Example 3, except that recycled 1,2-dichloroethane, which has a high water content, was used. As shown in Table 3, the iron and hydrogen bromide contents in 2-bromoethylbenzene were the same as in Comparative Example 3, but the content of nuclear brominated BEBS clearly increased due to the increased water content. This is thought to be due to the synergistic effect of impurities in the reaction system, which further promoted side reactions.
[0096] Comparative Example 5: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (16) A concentrated aqueous BEBS solution was synthesized in the same manner as in Examples 4 and 5, except that the concentration of sulfuric anhydride added dropwise to the reactor and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene were increased. As shown in Table 3, although the iron content, hydrogen bromide content, and water content in the reaction system were the same as in Examples 1 to 11, it is clear that the content of brominated BEBS was high. This is thought to be due to the promotion of side reactions by the high concentration of sulfuric anhydride.
[0097] Comparative Example 6: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (17) A concentrated BEBS aqueous solution was synthesized using the same procedure as in Comparative Example 5, except that recycled 1,2-dichloroethane with a high water content was used. As shown in Table 3, it is clear that the content of nuclear brominated BEBS further increased due to the increase in water content compared to Comparative Example 5.
[0098] Reference Example 1: Preparation of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (18) A concentrated aqueous BEBS solution was synthesized in the same manner as in Examples 4 and 5, except that the concentration of sulfuric anhydride in the reactor and the molar ratio of sulfuric anhydride to 2-bromoethylbenzene were reduced. As shown in Table 3, the iron content, hydrogen bromide content, and water content in the reaction system were low, so the content of brominated BEBS was low. However, despite the high reaction temperature, the reaction conversion rate was extremely low at 35%, and a large amount of the raw material 2-bromoethylbenzene remained. Therefore, it is clear that this product is not suitable as an industrial raw material (precursor) for sodium 4-styrenesulfonate.
[0099] Comparative Example 7 Production of 4-(2-bromoethyl)benzenesulfonic acid (BEBS) (18) Using a recycled product of 1,2-dichloroethane with a high water content, and 2-bromoethylbenzene with a high iron content, hydrogen bromide content and water content, similar to Comparative Examples 3 to 4, the same operations as in Reference Example 1 were performed in all other respects to synthesize a concentrated BEBS aqueous solution. It is clear that even when the concentration and molar ratio of sulfuric anhydride are low, if the iron content, hydrogen bromide content and water content in the reaction system exceed a certain concentration, the content of nuclear brominated BEBS increases. In addition, since the amount of sulfuric anhydride added is small, the reaction conversion rate is extremely low at 29.7% and is not at all suitable for practical use.
[0100]
Table 3
[0101] Example 12 Production of high-purity sodium 4-styrenesulfonate (1) <Synthesis of NaSS> 276.00 g of a 12% aqueous sodium hydroxide solution and 0.80 g of sodium nitrite were charged into a 2 L cylindrical glass separable flask equipped with a reflux condenser, a nitrogen inlet tube and a stirrer, and the temperature was raised to 70 °C while stirring. The internal temperature was maintained at 90 °C, and 462.00 g of a 48% aqueous sodium hydroxide solution and 708.40 g of a 70.4 wt%-BEBS acid aqueous solution obtained in Example 1 were each added dropwise over 3 hours while stirring under a nitrogen atmosphere. The resulting NaSS slurry was cooled to 30 °C and then solid-liquid separated by a centrifuge to obtain 310.80 g of a wet cake of NaSS. The NaSS contains impurities such as sodium bromide. Therefore, in the following examples and comparative examples, in order to quantify the amount of bound bromine, purification was performed as follows.
[0102] <Purification of NaSS> A 1 L cylindrical glass separable flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer was charged with 6.16 g of sodium hydroxide, 293.00 g of pure water, 0.28 g of sodium nitrite, and 308.00 g of the NaSS obtained above, and the mixture was stirred at 60°C for 1 hour under a nitrogen atmosphere. After cooling to room temperature over 3 hours, the mixture was subjected to solid-liquid separation using a centrifuge to obtain 272.10 g of a wet cake of purified NaSS. Approximately 100 g of the purified NaSS cake obtained above was dissolved in purified water to prepare a 5 wt% aqueous solution (based on pure content). This solution was passed through a column of strongly acidic cation exchange resin (Organo Corporation, Amberlite IR-120B, hydrochloric acid regenerated) and a column of strongly basic anion exchange resin (Organo Corporation, Amberlite IRA-402BL, sodium hydroxide regenerated), in that order, to obtain an aqueous styrene sulfonic acid solution. Because styrene sulfonic acid is prone to spontaneous polymerization after cation exchange, the aqueous solution after column distillation was maintained below 5°C, and after anion exchange, it was immediately neutralized with sodium hydroxide. The aqueous solution was concentrated using a rotary evaporator, and the precipitated crystals were filtered and vacuum dried at 60°C for 5 hours to obtain 64.60 g of high-purity NaSS crystals with a purity of 99.5 wt% and a water content of 0.5 wt%. The bromine content in the high-purity NaSS, i.e., inorganic (unbound) bromine content, determined by ion chromatography was less than 1 ppm. Furthermore, HPLC analysis of organic impurities such as isomers that may be contained in the above-mentioned high-purity NaSS crystals revealed the following: (a) sodium orthostyrenesulfonate 0.00%, (b) sodium 4-(2-bromoethyl)benzenesulfonate 0.00%, (c) sodium metastyrenesulfonate 0.01%, (d) sodium bromostyrenesulfonate 0.01%, and (e) sodium 4-(2-hydroxyethyl)benzenesulfonate 0.00% (however, this is the area ratio when the sum of the HPLC peak areas of the above-mentioned organic impurities and NaSS is taken as 100). From the molecular weight of NaSS (206.2 g / mol), the molecular weight of sodium bromostyrenesulfonate (285.1 g / mol), the atomic weight of Br (79.9 g / mol), and the above HPLC area ratio (assuming it is approximately the molar ratio), the bromine content derived from sodium bromostyrenesulfonate in high-purity NaSS can be estimated as follows. 1,000,000×79.9×0.01 / (285.1×0.01 + 206.2×99.99) ≒ 39 ppm On the other hand, the total bromine content of the high-purity NaSS, that is, the result of quantifying the bound bromine by combustion decomposition ion chromatography, was 108 ppm, which was much higher than the above. That is, it was suggested that there was a quantitative error due to the extremely small peak of the above sodium bromostyrenesulfonate, or the existence of bound bromine other than sodium bromostyrenesulfonate, such as positional isomers. However, compared with Comparative Examples 8 to 11, the total bromine amount was clearly less (Table 4). This is considered to be because BEBS with a low content of nuclear brominated BEBS was used as the precursor. Furthermore, by the following method, the high-purity NaSS was polymerized to induce PSS, and the change in bromine ion concentration over time (the existence of unstable bound bromine) was confirmed.
[0103] <Synthesis of Poly NaSS> In a 500 ml glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, 250.00 g of pure water, 30.02 g of the high-purity NaSS obtained above, and 1.00 g of a water-soluble azo radical polymerization initiator V-50 were collected and dissolved at room temperature. Subsequently, after repeated deoxygenation by aspirator suction and nitrogen introduction, polymerization was carried out in a 60 °C water bath for 24 hours while stirring under a nitrogen atmosphere. At this point, the polymerization conversion rate of NaSS determined by GPC was 100%. Subsequently, under a nitrogen stream, 1.64 g of a 48 wt% aqueous sodium hydroxide solution was added, and stirring was continued at 60 °C for 24 hours while maintaining the solution pH ≥ 13. The number average molecular weight Mn of poly NaSS determined by GPC was 114,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.50).
[0104] <Preparation and Stability Confirmation of PSS> The obtained aqueous poly-NaSS solution was treated with an ultrafiltration module (Vivaflo 200 manufactured by Sartorius, molecular weight cut-off 50,000), and then passed through a strongly acidic cation exchange resin column (Amberlite IR-120B manufactured by Organo, regenerated with hydrochloric acid) and a strongly basic anion exchange resin column (Amberlite IRA-402BL manufactured by Organo, regenerated with sodium hydroxide) in that order to obtain an aqueous PSS solution. About 1 g of the aqueous solution was precisely weighed, dried in vacuo at 100 °C for 3 hours to calculate the resin content, and then the resin content was adjusted with pure water to obtain 230.01 g of a 10.00 wt% aqueous polystyrene sulfonic acid solution. The number average molecular weight of PSS was 114,000, the weight average molecular weight was 282,000 (Mw / Mn = 2.47), the bromide ion concentration determined by ion chromatography was less than 1 ppm, and the sodium content determined by ICP-AES was less than 1 ppm. That is, free (unbound) bromine was sufficiently removed. On the other hand, about 10 g of the PSS aqueous solution was taken, dried in vacuo at 110 °C for 3 hours to obtain PSS solid, and as a result of analyzing the total bromine content by decomposition combustion ion chromatography, it was 111 ppm. The total chlorine content in the PSS solid was less than 1 ppm. The above PSS aqueous solution was sealed in small portions in glass sample bottles and aged in an oven at 70 °C. As a result of tracking the change in bromide ion concentration by ion chromatography, as shown in Table 4, it is clear that the increase in bromide ions over time is significantly suppressed compared to Comparative Examples 8 to 11. It is considered that this is because the amount of bound bromine contained in NaSS is small, that is, the nuclear brominated compounds that may be contained in BEBS, the precursor, were reduced. In addition, as long as BEBS is used as the precursor, the possibility of chlorine remaining in NaSS and its polymer is low. On the other hand, when 4-(2-chloroethyl)benzenesulfonic acid (for example, JP-A-9-40633) is used as the precursor, it is considered that inorganic and organic chlorine may remain, similar to BEBS.
[0105] Example 13 Production of High-Purity Sodium 4-Styrenesulfonate (2) <Synthesis of NaSS> Reaction and the like were carried out under the same conditions as in Example 12 in terms of charged weight and the like, except that the 69.9 wt%-BEBS aqueous solution obtained in Example 2 was used, and 302.20 g of a wet cake of NaSS was obtained.
[0106] <Purification of NaSS> Purification was carried out under the same conditions as in Example 12 except that the wet cake of NaSS obtained above was used, and 66.02 g of dry crystals of high-purity NaSS were obtained. The purity was 99.5 wt%, the moisture was 0.5 wt%, the bromine content in the high-purity NaSS, that is, the inorganic bromine content analyzed in an aqueous solution was less than 1 ppm, and the total bromine content was 46 ppm. It is clear that the total bromine amount is less than that in Comparative Examples 8 to 11 (Table 4). This is considered to be because BEBS with a low content of nuclear brominated BEBS was used as a precursor. Subsequently, in the same manner as in Example 12, NaSS was polymerized to induce PSS, and the change in bromine ion concentration over time was confirmed.
[0107] <Synthesis of poly-NaSS> NaSS was polymerized under the same conditions as in Example 12 in terms of charged weight and the like except that the high-purity NaSS crystals obtained above were used, and an aqueous solution of poly-NaSS with a number-average molecular weight Mn of 112,000 and a weight-average molecular weight Mw of 281,000 (Mw / Mn = 2.51) was obtained.
[0108] <Preparation of PSS and Confirmation of Stability> Ultrafiltration and ion exchange treatment were carried out under the same conditions as in Example 12 except that the aqueous solution of poly-NaSS obtained above was used, and 238.96 g of a 10.00 wt% PSS aqueous solution was obtained. The number-average molecular weight was 112,000, the weight-average molecular weight was 281,000 (Mw / Mn = 2.51), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. PSS solid was obtained in the same manner as in Example 12, and as a result of analyzing the total bromine content, it was 47 ppm, which was decreased compared to Example 12. In addition, the total chlorine content in the PSS solid was less than 1 ppm. Subsequently, in the same manner as in Example 12, the above PSS aqueous solution was aged, and as a result of tracking the change in bromine ion concentration, as shown in Table 4, it was clear that the increase in bromine ions over time was significantly suppressed compared to Comparative Examples 8 to 11. It is considered that this is because the amount of bound bromine contained in NaSS is small, that is, the nuclear brominated species that may be contained in BEBS, which is the precursor, was reduced.
[0109] Example 14 Production of High-Purity Sodium 4-Styrenesulfonate (3) <Synthesis of NaSS> Reactions and the like were carried out under the same conditions as in Example 12 for all aspects such as the charged weight, except that the 71.3 wt%-BEBS aqueous solution obtained in Example 7 above was used, and 316.10 g of a wet cake of NaSS was obtained.
[0110] <Purification of NaSS> Purification was carried out under the same conditions as in Example 12 for all aspects such as the charged weight, except that the NaSS obtained above was used, and 63.60 g of dry crystals of high-purity NaSS was obtained. The purity was 99.5 wt%, the water content was 0.5 wt%, the bromine content in the high-purity NaSS, that is, the inorganic bromine content analyzed in an aqueous solution, was less than 1 ppm, and the total bromine content was 302 ppm. Because BEBS with a large amount of nuclear brominated BEBS was used, the total bromine content is higher compared to Examples 12 and 13, but it is clearly less compared to Comparative Examples 8 to 11 (Table 4). Subsequently, in the same manner as in Example 12, NaSS was polymerized to induce PSS, and the change in bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0111] <Synthesis of PolyNaSS> Polymerization of NaSS was carried out under the same conditions as in Example 12 for all aspects such as the charged weight, except that the high-purity NaSS crystals obtained above were used, and an aqueous solution of PolyNaSS with a number average molecular weight Mn of 113,000 and a weight average molecular weight Mw of 283,000 (Mw / Mn = 2.50) was obtained.
[0112] <Preparation and Stability Confirmation of PSS> Ultrafiltration and ion exchange were performed in the same manner as in Example 12, except that the poly(NaSS) aqueous solution obtained above was used, yielding 241.95 g of a 10.00 wt% PSS aqueous solution. The number-average molecular weight was 113,000, the weight-average molecular weight was 283,000 (Mw / Mn = 2.50), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. PSS solid was obtained in the same manner as in Example 12, and the total bromine content was analyzed, resulting in a value of 315 ppm, and the total chlorine content was less than 1 ppm. Next, in the same manner as in Example 12, the PSS aqueous solution was aged and the change in bromine ion concentration was tracked. As a result, as shown in Table 4, it is clear that the increase in bromine ions over time was significantly suppressed compared to Comparative Examples 8 to 11. This is thought to be because the amount of bound bromine contained in NaSS is small, that is, the nuclear brominated compounds that may be contained in the precursor BEBS are reduced.
[0113] Example 15 Preparation of ethyl styrenesulfonate (ETSS) (1) <Synthesis of 4-styrenesulfonyl chloride (ClSS)> In a 3 L four-necked glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, 300.00 g (1.45 mol) of the high-purity NaSS crystals obtained under the conditions of Example 12, 600.00 g of toluene, 106.00 g (1.44 mol) of N,N-dimethylformamide, and 0.12 g (0.1 mmol) of the antioxidant Irganox (registered trademark) 1010 were charged, and the mixture was stirred for 30 minutes under a nitrogen atmosphere while maintaining the internal temperature at 0 °C. Subsequently, while controlling the internal temperature so that it did not exceed 5 °C, 236.0 g (1.94 mol) of thionyl chloride was added dropwise over 2 hours, and stirring was continued for another 3 hours. Next, while controlling the internal temperature so that it did not exceed 20 °C, 750.00 g of pure water was added, and after sufficient stirring, the mixture was allowed to stand, and the separated aqueous layer was discarded. 750.00 g of a 20 wt% aqueous sodium chloride solution was added to the remaining organic layer, and after sufficient stirring, the mixture was allowed to stand, and the separated aqueous layer was discarded. Then, while controlling the internal temperature so that it did not exceed 10 °C, nitrogen was blown into the reaction solution for 12 hours while stirring to remove the components derived from thionyl chloride. Thereafter, 750.00 g of pure water was added to the organic layer again, and the organic layer was repeatedly washed with water until the electrical conductivity of the aqueous layer became 1 μS / cm or less, and 760.00 g of a ClSS solution was obtained. 1 The ClSS concentration determined by 1H-NMR was 36.2 wt%. That is, the pure content of ClSS was 275.10 g (1.36 mol), and the yield based on the charged NaSS was 94%.
[0114] <Synthesis of ETSS> A 200 ml four-neck glass flask equipped with a reflux condenser, nitrogen inlet, and stirrer was charged with 38.5 g (0.069 mol) of the ClSS solution obtained above, 9.2 g (0.200 mol) of ethanol, and 6 mg (0.005 mmol) of the antioxidant Irganox® 1010. The internal temperature was controlled so as not to exceed 0°C. An aqueous solution consisting of 15.4 g (0.132 mol) of 48 wt% potassium hydroxide aqueous solution and 9.2 g of pure water was added dropwise over 5 hours, and the mixture was aged for another 5 hours to induce esterification. During this time, the internal temperature was controlled so as not to exceed 20°C. Next, 100.00 g of pure water was added, the mixture was stirred, and the mixture was allowed to stand. The aqueous layer containing potassium chloride and other elements was discarded, and the mixture was then washed with 20 wt% saline. Further pure water was added, and the mixture was washed until the ionic conductivity of the aqueous layer reached 1.00 μS / cm or less, and the organic layer was recovered. Toluene was distilled off under reduced pressure using a rotary evaporator at 40°C to obtain 12.01 g of ETSS. The purity based on area % determined by gas chromatography was 94.00% (the main impurity was toluene contained in the ClSS solution), and the yield based on ClSS was 77%. The bromine content in the ETSS determined by ion chromatography, i.e., the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 84 ppm, clearly indicating a lower bromine content than in Comparative Examples 12 to 14 (Table 4). This is thought to be due to the use of NaSS derived from BEBS with a low content of nuclear brominated BEBS as the raw material. Next, ETSS was polymerized to form PSS using the following method, and the change in bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0115] <Synthesis of PolyETSS> In a 300 ml four-necked glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, 10.75 g (46.80 mmol) of ETSS obtained above, 40.00 g of anisole, 0.15 g (0.94 mmol) of 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), and 0.40 g (2.39 mmol) of azobisisobutyronitrile were collected. After deoxygenation by repeating evacuation and nitrogen introduction while stirring with a magnetic stir bar, polymerization was carried out at 110 °C for 20 hours and then at 135 °C for 2 hours under a nitrogen atmosphere to prepare poly-ETSS.
[0116] <Preparation and Stability Confirmation of PSS> After allowing the above reaction solution to cool to 100 °C, 75.00 g (93.75 mmol) of a 5 wt% aqueous sodium hydroxide solution was added and stirred for 5 hours. Then, the insoluble matter was filtered off, and the aqueous layer containing poly-NaSS was recovered by liquid separation operation. While vigorously stirring the aqueous solution, it was slowly dropped into 2 L of acetone, and the precipitated polymer was vacuum dried at 110 °C for 10 hours to recover 3.67 g of poly-NaSS (yield 38% based on ETSS). The number average molecular weight of poly-NaSS was 9,000, and the weight average molecular weight was 11,000 (Mw / Mn = 1.22). The poly-NaSS was dissolved in pure water and treated with an ultrafiltration module (Vivaflo 200 manufactured by Sartorius, molecular weight cut-off 5,000). Then, ion exchange treatment was carried out in the same manner as in Example 12 to obtain 26.77 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight was 9,000, the weight average molecular weight was 11,000 (Mw / Mn = 1.22), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. That is, it can be said that free bromine not bound to the polymer was sufficiently removed by the ion exchange treatment. Similar to Example 12, the above PSS was aged, and as a result of tracking the change in bromine ion concentration, as shown in Table 4, it was clear that the increase in bromine ions over time was significantly suppressed compared to Comparative Examples 12 to 14. This is presumably because the amount of bound bromine contained in ETSS is small, that is, the nuclear brominated species that may be contained in BEBS, which is the precursor, was reduced.
[0117] Example 16 Production of Ethyl Styrenesulfonate (ETSS) (2) <Synthesis of ClSS> Using the high-purity NaSS crystals obtained in Example 13 and reducing the scale to 1 / 10, 75.00 g of ClSS solution was obtained under the same conditions as in Example 15. 1 The ClSS concentration determined by 1H-NMR was 35.9 wt%. That is, the pure content of ClSS was 26.93 g, and the yield based on the charged NaSS was 92%.
[0118] <Synthesis of ETSS> Using the ClSS obtained above, ETSS was synthesized under the same conditions as in Example 15, and 11.90 g of ETSS was obtained. The purity based on the area% determined by gas chromatography was 95.00% (the main impurity was toluene contained in the ClSS solution), and the yield based on ClSS was 78%. The bromine content in the ETSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 51 ppm. It was clear that the bromine content was less compared to Comparative Examples 12 to 14 (Table 4). This is presumably because NaSS derived from BEBS with a low content of nuclear brominated BEBS was used as the raw material. Subsequently, in the same manner as in Example 15, ETSS was polymerized to induce PSS, and the change in bromine ion concentration over time was confirmed.
[0119] <Synthesis of PolyETSS> Using the ETSS obtained above, ETSS was polymerized under the same conditions as in Example 15 to prepare polyETSS.
[0120] <Preparation of PSS and Confirmation of Stability> Using the polyETSS obtained above, the same operations as in Example 15 were performed to obtain 26.98 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight was 9,000, the weight average molecular weight was 11,000 (Mw / Mn = 1.22), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above PSS aqueous solution was aged, and as a result of tracking the change in bromide ion concentration, as shown in Table 4, it is clear that the increase in bromide ions over time is significantly suppressed compared to Comparative Examples 12 to 14. This is presumably because the amount of bound bromine contained in ETSS is small, that is, because the nuclear brominated species that may be contained in BEBS, which is the precursor, has been reduced.
[0121] Example 17 Production of Ethyl Styrenesulfonate (ETSS) (3) <Synthesis of ClSS> Reactions and the like were carried out under the same conditions as in Example 16 in all respects such as the charged weight, except that the high-purity NaSS crystals obtained in Example 14 were used, and 76.30 g of a ClSS solution was obtained. 1 The ClSS concentration determined by 1H-NMR was 35.50% by weight. That is, the pure ClSS content was 27.09 g, and the yield based on the charged NaSS was 92%.
[0122] <Synthesis of ETSS> Reactions and the like were carried out under the same conditions as in Example 16 in all respects, except that the ClSS obtained above was used, and 12.10 g of ETSS was obtained. The purity based on the area% determined by gas chromatography was 95.00% (the main impurity was toluene contained in the ClSS solution), and the yield based on ClSS was 80%. The bromine content in the ETSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 338 ppm. It is clear that the bromine content is less compared to Comparative Examples 12 to 14 (Table 4). However, since BEBS with a large amount of nuclear brominated BEBS was used as the high-purity NaSS raw material, the total bromine content increased compared to Examples 15 and 16. Subsequently, similar to Example 15, ETSS was polymerized to induce PSS, and the change in bromide ion concentration over time was confirmed.
[0123] <Synthesis of PolyETSS> Reactions and the like were carried out under the same operations as in Example 16 in all respects, except that the ETSS obtained above was used, and polyETSS was prepared by polymerizing ETSS.
[0124] <Preparation and Stability Confirmation of PSS> Except for using the polyETSS obtained above, 26.65 g of a 10.00 wt% PSS aqueous solution was obtained by the same operations as in Example 16. The number average molecular weight was 9,000, the weight average molecular weight was 11,000 (Mw / Mn = 1.22), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 15, the above PSS aqueous solution was aged and the change in bromine ion concentration was traced. As shown in Table 4, it was clear that the increase in bromine ions over time was significantly suppressed compared to Comparative Examples 12 to 14. This is presumably because the amount of bound bromine contained in ETSS is small, that is, the nuclear brominated product that may be contained in BEBS, which is the precursor, was reduced.
[0125] Example 18 Production of High-Purity Neopentyl Styrenesulfonate (NPSS) (1) <Synthesis of NPSS> 54.00 g (0.60 mol) of neopentyl alcohol and 171.3 g (2.14 mol) of pyridine were placed in a 1 L glass four-necked flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, and stirred and dissolved with a magnetic stirrer while maintaining the internal temperature at 0 °C. While controlling the internal temperature so that it did not exceed 0 °C, 323.21 g (0.58 mol) of the 36.20 wt%-ClSS solution obtained in Example 15 was added dropwise to the reactor over 2.5 hours and reacted. After distilling off the excess pyridine and toluene using an evaporator, the contents were poured into 1 L of hexane and cooled to -15 °C to recover white crystals. The white crystals were recrystallized and purified using a mixed solvent of hexane:toluene = 1:1 volume ratio to obtain 37.5 g of white crystals of NPSS. The yield based on ClSS was 25%, 1 The purity determined by 1H-NMR (internal standard substance 1,3,5-trimethylbenzene) was 97.5%. The bromine content in the NPSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 122 ppm. It was clear that the bromine content was less compared to Comparative Example 15 (Table 4). This is presumably because NaSS derived from BEBS with a low content of nuclear brominated BEBS was used as a raw material. Furthermore, by the following method, NPSS was polymerized to induce PSS, and the change in bromine ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0126] <Synthesis of poly NPSS> Into a 200 ml four-necked glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, 10.00 g (39.32 mmol) of NPSS obtained above, 40.00 g of N,N-dimethylformamide, and 325 mg (1.98 mmol) of azobisisobutyronitrile were collected. After deoxygenation by repeating evacuation and nitrogen introduction while stirring, polymerization was carried out at 70 °C for 25 hours under a nitrogen atmosphere. While vigorously stirring the polymerization solution, it was slowly dropped into 1 L of hexane to isolate poly NPSS. The polymer was dissolved again in chloroform and dropped into hexane, which is a poor solvent, to purify the polymer. The wet polymer was vacuum dried at 90 °C for 10 hours to recover 7.10 g of poly NPSS (yield 71% based on NPSS). The number average molecular weight Mn measured by GPC was 18,000, and the weight average molecular weight Mw was 45,000 (Mw / Mn = 2.50).
[0127] <Synthesis and stability confirmation of PSS> After dissolving 7.10 g of the poly NPSS obtained above in 60.0 g of dichloromethane, 14.76 g of trimethylsilyl iodide (2.5 equivalents relative to the neopentyl group of sulfonic acid) was added, and the mixture was stirred at room temperature for 4 hours. Subsequently, dichloromethane was distilled off under reduced pressure, and the recovered polymer was put into a mixed solution consisting of 40 ml of 1N hydrochloric acid and 40 ml of methanol, stirred at room temperature for 2 hours, and then the solvent was distilled off under reduced pressure to obtain PSS. The obtained PSS was dissolved in ion-exchanged water, treated with an ultrafiltration module (Vivaflo 200 manufactured by Sartorius, molecular weight cut-off 10,000), and then subjected to ion-exchange treatment in the same manner as in Example 15 to obtain 56.80 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight was 18,000, the weight average molecular weight was 45,000 (Mw / Mn = 2.50), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. That is, it can be said that free bromine compounds not bound to the polymer were sufficiently removed by the purification treatment. Similar to Example 12, the above PSS aqueous solution was aged, and as a result of tracking the change in bromide ion concentration, as shown in Table 4, it is clear that the increase in bromide ions over time is significantly suppressed compared to Comparative Example 15. This is presumably because the amount of bound bromine in NPSS is small, that is, because the nuclear brominated compounds that may be contained in BEBS, the precursor, are reduced.
[0128] Example 19 Production of High-Purity Sodium 4-Styrenesulfonyl(trifluoromethylsulfonylimide) (TfNS-Na) (1) <Synthesis of TfNS-Na> 14.92 g (98.07 mmol) of trifluoromethanesulfonamide, 116.00 g of ethyl acetate, 0.62 g (4.97 mmol) of 4-dimethylaminopyridine, and 1.02 g of tert-butylcatechol were placed in a 500 ml four-necked glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, stirred and dissolved at room temperature, and then 21.24 g (198.39 mmol) of sodium carbonate was added. After raising the internal temperature to 50 °C, 54.88 g (98.03 mmol) of the 36.2 wt%-ClSS solution obtained in Example 15 was added dropwise over 1 hour while maintaining the internal temperature at 50 - 60 °C. After further aging at 60 °C for 4 hours, it was cooled to 35 °C, 90.00 g of ion-exchanged water was added, stirred vigorously, allowed to stand, separated, and the aqueous layer containing sodium chloride was discarded. Further, 50.00 g of a 20 wt% aqueous sodium chloride solution was added, stirred vigorously, allowed to stand, separated, and the aqueous layer was discarded. 60.00 g of toluene, a non-solvent, was added to the organic layer to form a homogeneous solution, and then ethyl acetate, a good solvent, was distilled off under reduced pressure. The precipitated crystals were filtered off and vacuum dried at room temperature for 24 hours to obtain 25.34 g (yield 73%) of TfNS-Na.
[0129] <Purification of TfNS-Na> The TfNS-Na obtained above was dissolved in ion-exchanged water to prepare a 5 wt% aqueous solution. While taking care to ensure that the temperature of the aqueous solution did not exceed 10°C, the solution was subjected to cation and anion exchange treatment in the same manner as in Example 12 to obtain a TfNS-H aqueous solution. Because TfNS-H after cation exchange is prone to spontaneous polymerization, the aqueous solution after elution from the column was kept at 5°C or below, and immediately after anion exchange, it was neutralized with sodium hydroxide. Water was distilled off from the aqueous solution using a rotary evaporator, and the precipitated crystals were filtered out and dried in vacuum at 60°C for 5 hours to obtain 1.30 g of high-purity TfNS-Na2. 1 The purity determined by H-NMR (internal standard 1,3,5-trimethylbenzene) was 99.5% by weight, the water content was 0.5% by weight, the bromine content determined by ion chromatography, i.e., the inorganic bromine content analyzed in aqueous solution was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 101 ppm. It is clear that the total bromine content is lower than in Comparative Example 16 (Table 4). This is thought to be due to the use of sodium styrenesulfonate derived from BEBS with a low content of nuclear brominated BEBS as a raw material. Furthermore, TfNS-Na was polymerized by the following method, and the change in bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0130] <Synthesis of PolyTfNS-H> The monomer aqueous solution prepared above, consisting of 20.00 g (58.71 mmol) of TfNS-Na dissolved in 90.00 g of ion-exchanged water, and the radical polymerization initiator aqueous solution, consisting of 0.10 g (0.44 mmol) of ammonium persulfate dissolved in 10.00 g of ion-exchanged water, were deoxygenated by repeatedly reducing the pressure with an aspirator and then introducing nitrogen. The aqueous solutions were simultaneously added dropwise over 3 hours to a 200 ml glass four-neck flask equipped with a reflux condenser, nitrogen inlet, and stirrer, while polymerization was carried out at a bath temperature of 85°C. The mixture was then aged for another 2 hours at 85°C. The polymerization conversion measured by GPC was 98.7%, the number average molecular weight was 35,000, and the weight average molecular weight was 82,000 (Mw / Mn = 2.34). By subjecting the aqueous poly(TfNS-Na) solution to ultrafiltration and ion exchange treatment in the same manner as in Example 18, 146.88 g of a 10.00 wt% aqueous poly(TfNS-H) solution was obtained. The bromide ion concentration determined by ion chromatography was less than 1 ppm, and the sodium content determined by ICP-AES was less than 1 ppm.
[0131] <Stability of poly(TfNS-H)> Similar to Example 12, as a result of tracking the change in bromide ion concentration by ion chromatography, as shown in Table 4, it is clear that the increase in bromide ions over time is significantly suppressed compared to Comparative Example 16. This is presumably because the amount of bound bromine in TfNS-Na is small, that is, because the nuclear brominated species that may be contained in BEBS, the precursor, has been reduced.
[0132] Example 20 Production of High-Purity Lithium 4-Styrenesulfonate (LiSS) (1) <Synthesis of LiSS> A 1 L cylindrical glass separable flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer was charged with 130.60 g (3.23 mol) of lithium hydroxide monohydrate, 0.60 g (0.009 mol) of sodium nitrite, and 351.00 g of ion-exchanged water, and the temperature was raised to 70 °C while stirring. The internal temperature was maintained at 90 °C, and 457.75 g (1.21 mol) of the 70.20 wt%-BEBS aqueous solution obtained in Example 4 above was added dropwise over 1 hour while stirring under a nitrogen atmosphere, and the mixture was further aged for 0.5 hour. After cooling the reaction solution to 20 °C over 3 hours, it was aged as it was for 2 hours, and the resulting slurry of LiSS was separated into solid and liquid by a centrifuge to obtain 199.70 g (0.89 mol) of a wet cake of LiSS with a purity of 85.0%.
[0133] <Purification of LiSS> 2 L of the above wet cake and 1 L of acetone were taken in a 2 L glass beaker, stirred at room temperature for 1 hour, and then the wet LiSS was recovered using a Buchner funnel. The recovered wet LiSS was put into 1 L of acetone again, stirred at room temperature for 1 hour, and then the wet LiSS was recovered using a Buchner funnel. Further, it was vacuum dried at 60 °C for 10 hours in an oven to obtain 73.50 g of high purity LiSS. The purity was 98.7 wt%, the moisture content was 1.30 wt%, and the bromine content in the high purity LiSS determined by ion chromatography, that is, the inorganic bromine content analyzed in an aqueous solution, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 296 ppm. It was revealed that the total bromine content was less than that in Comparative Example 17 (Table 4). This is presumably because BEBS with a low content of nuclear brominated BEBS was used as the raw material. Furthermore, LiSS was polymerized to induce PSS by the following method, and the change in bromine ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0134] <Synthesis of poly LiSS> 250.00 g of pure water, 30.00 g (0.16 mol) of the high purity LiSS obtained above, and 2.10 g (0.008 mol) of a water-soluble azo radical polymerization initiator V-50 were taken in a 500 ml glass flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, and dissolved at room temperature. Subsequently, after repeated deoxygenation by aspirator suction and nitrogen introduction, polymerization was carried out in a 60 °C water bath under a nitrogen atmosphere with stirring for 24 hours. At this point, the polymerization conversion rate of LiSS was 100%. Subsequently, 1.70 g of a 40 wt% lithium hydroxide aqueous solution was added under a nitrogen stream, and stirring was continued at 60 °C for 24 hours while maintaining the solution pH ≧ 13 or higher to obtain an aqueous poly LiSS solution. The number average molecular weight Mn was 65,000, and the weight average molecular weight Mw was 161,000 (Mw / Mn = 2.48).
[0135] <Preparation of PSS and confirmation of stability> 236.88 g of a 10.00 wt% PSS aqueous solution was obtained by subjecting the aqueous poly LiSS solution obtained above to ultrafiltration and ion exchange treatment under the same conditions as in Example 18. The bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, as a result of tracking the bromine ion concentration by ion chromatography, as shown in Table 4, it is clear that the increase in bromine ions over time is significantly suppressed compared to Comparative Example 17. This is presumably because the amount of bound bromine in LiSS is small, that is, the nuclear brominated species that may be contained in BEBS as a precursor is reduced.
[0136] Example 21 Production of Sodium Styrenesulfonate / Styrene Copolymer (ST-3510) <Synthesis of NaSS / Styrene Copolymer> Into a 500 ml three-necked flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, 26.60 g (purity 88.5%, 114.17 mmol) of crude NaSS obtained in Example 12, 121.00 g of ion-exchanged water, 69.89 g of 2-propanol, 6.37 g (60.55 mmol) of styrene, and 0.92 g (3.36 mmol) of a water-soluble azo radical polymerization initiator V-50 were charged and dissolved, and oxygen was removed by repeating vacuum degassing and nitrogen introduction. Thereafter, the flask was immersed in a warm bath at 60 °C and polymerized with stirring for 25 hours. The polymerization conversion rate of sodium styrenesulfonate was 100%, the polymerization conversion rate of styrene was 98%, the number average molecular weight was 33,000, the weight average molecular weight was 74,000 (Mw / Mn = 2.24), and the copolymer composition calculated from the polymerization conversion rate was a NaSS / St = 66 / 34 molar ratio. Isopropanol and water were distilled off under reduced pressure using a rotary evaporator to obtain a 15 wt% polymer aqueous solution.
[0137] <Synthesis of Styrenesulfonic Acid / Styrene Copolymer> The above-mentioned NaSS / styrene copolymer was subjected to ultrafiltration and ion exchange treatment under the same conditions as in Example 19 to obtain 231.28 g of a 10.0 wt% aqueous solution of styrenesulfonic acid / styrene copolymer. The bromine ion concentration was less than 1 ppm and the sodium content was less than 1 ppm.
[0138] <Stability of Styrenesulfonic Acid / Styrene Copolymer> Similar to Example 12, the aqueous solution of the styrenesulfonic acid / styrene copolymer obtained above was aged, and as a result of tracking the change in the bromide ion concentration, as shown in Table 4, it was revealed that it had the same stability as Example 12. Since the amount of bound bromine contained in NaSS is small, it is considered that the nuclear brominated compound that may be contained in BEBS, which is the precursor, was reduced.
[0139] Example 22 Production of sodium styrenesulfonate / methacrylic acid copolymer <Synthesis of NaSS / methacrylic acid copolymer> 35.00 g (purity 88.5%, 150.22 mmol) of the unpurified NaSS obtained in Example 12, 250.00 g of ion-exchanged water, 3.35 g (38.52 mmol) of methacrylic acid, and 2.50 g (9.13 mmol) of a water-soluble azo radical polymerization initiator V-50 were charged into a 500 ml three-necked flask equipped with a reflux condenser, a nitrogen inlet tube, and a stirrer, dissolved, and deoxygenated by repeating vacuum degassing and nitrogen introduction. Then, the flask was immersed in a warm bath at 60 °C and polymerized for 25 hours while stirring. The polymerization conversion rate of NaSS was 100%, the polymerization conversion rate of methacrylic acid was 96%, the number average molecular weight was 46,000, the weight average molecular weight was 129,000 (Mw / Mn = 2.80), and the copolymer composition calculated from the polymerization conversion rate was a NaSS / MAA = 80 / 20 molar ratio. Water was distilled off under reduced pressure using a rotary evaporator to obtain a 15 wt% polymer aqueous solution.
[0140] <Synthesis of styrenesulfonic acid / methacrylic acid copolymer> The above NaSS / methacrylic acid copolymer was subjected to ultrafiltration and ion exchange treatment under the same conditions as in Example 19 to obtain 262.26 g of a 10.0 wt% aqueous solution of the styrenesulfonic acid / methacrylic acid copolymer. The bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm.
[0141] <Stability of styrenesulfonic acid / methacrylic acid copolymer> Similar to Example 12, the above styrenesulfonic acid / methacrylic acid copolymer aqueous solution was aged, and as a result of tracking the change in bromide ion concentration, as shown in Table 4, it was revealed that it has the same stability as Example 12. Since the amount of bound bromine contained in NaSS is small, it is considered that the nuclear brominated product that may be contained in BEBS, which is the precursor, was reduced.
[0142] Example 23 Production of Lithium Bis-(4-styrenesulfonyl)imide (BVBSI-Li) (1) <Synthesis of 4-styrenesulfonamide> Into a 300 mL glass flask reactor equipped with a reflux condenser, a nitrogen inlet tube, and a dropping tube, 30.0 g (54.20 mmol) of the ClSS solution synthesized in Example 15 and 30.00 g of tetrahydrofuran were collected and stirred and dissolved at room temperature. This solution was cooled to 0 °C, and 30.00 g (493.25 mmol) of a 28% aqueous ammonia solution (manufactured by Kishida Chemical) was added dropwise over 1 hour. After the addition was complete, the mixture was stirred at room temperature for 2 hours. After the reaction was complete, 30.00 g of ion-exchanged water and 30.00 g of ethyl acetate were added, and a liquid separation operation was performed to obtain an organic layer containing 4-styrenesulfonamide. This organic layer was concentrated to obtain 6.05 g (yield 65%) of a white solid of 4-styrenesulfonamide.
[0143] <Synthesis of BVBSI-Li> Into a 100 ml glass flask reactor equipped with a reflux condenser, a nitrogen inlet tube, and a dropping tube, 5.00 g (28.96 mmol) of the 4-styrenesulfonamide obtained above, 0.55 g (65.72 mmol) of lithium hydride, and 30.00 g of dehydrated tetrahydrofuran were collected and stirred at room temperature under a nitrogen atmosphere. Next, 16.00 g (28.59 mmol) of the ClSS solution synthesized in Example 15 was added dropwise to the above slurry solution at room temperature. After the addition was complete, the temperature was raised to 60 °C and stirred for 3 hours. The solvent was distilled off using a rotary evaporator to recover a white solid. The white solid was washed with diethyl ether and then recrystallized using methanol to obtain 6.74 g of white crystals of BVBSI-Li, a yield of 64% based on ClSS, 1The purity determined by 1H-NMR (internal standard substance: 1,3,5-trimethylbenzene) was 94.0%. The bromine content in the high-purity BVBSI-Li determined by ion chromatography, that is, the inorganic bromine content analyzed in an aqueous solution, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 121 ppm.
[0144] Synthesis Example 2 Production of Lithium Polystyrene Sulfonate Crosslinked Product 2.00 g (10.21 mmol) of LiSS obtained in Example 20, 0.50 g (1.06 mmol) of BVBSI-Li obtained in Example 23, and 0.005 g (0.018 mmol) of water-soluble azo polymerization initiator V-50 were dissolved in 3.50 g of ion-exchanged water to prepare a mixed monomer solution. The monomer solution was dropped onto a transparent glass plate (thickness: 1.5 mm, 5 cm × 5 cm square) on which a PET film spacer (thickness: 0.5 mm, with a 3 cm × 3 cm window cut out in the center of the 5 cm × 5 cm square film) was placed. Then, the same transparent glass plate was overlapped from above to exclude the excess monomer solution. After fixing the two glass plates with a metal clip, LED light with a wavelength of 365 nm was irradiated for 3.0 hours from a distance of 5 cm in the direction perpendicular to the glass surface. The illuminance at a position 5 cm away from the LED irradiation surface in the vertical direction was 100 mW / cm 2 . The metal clip was removed, and the glass plate was immersed in a 1 L poly beaker filled with ion-exchanged water. The beaker was immersed in an ultrasonic cleaner and ultrasonic-treated at room temperature for 10 minutes. As a result, the glass plate came off, and a swollen sheet-like crosslinked product was obtained. That is, by using LiSS and BVBSI-Li with reduced bound bromine, an electrolyte membrane or coating film in which the release of bromine over time is suppressed can be easily formed.
[0145]
Table 4
[0146] Comparative Example 8 Production of Sodium 4-Styrenesulfonate (NaSS) (4) <Production of NaSS> Except for using the 69.7 wt%-BEBS aqueous solution obtained in Comparative Example 5, the same operations as in Example 12 were carried out to obtain 311.60 g of a wet cake of NaSS.
[0147] <Purification of NaSS> Except for using the wet cake of NaSS obtained above, the same operations as in Example 12 were carried out to obtain 273.70 g of a wet cake of purified NaSS. The purified NaSS was subjected to ion exchange treatment in the same manner as in Example 12 to obtain 32.80 g of dry crystals of high-purity NaSS. The purity was 99.3 wt% and the moisture was 0.7 wt%. The organic impurities such as isomers analyzed by high performance liquid chromatography (HPLC) were (a) sodium ortho-styrenesulfonate 0.00%, (b) sodium 4-(2-bromoethyl)benzenesulfonate 0.00%, (c) sodium meta-styrenesulfonate 0.32%, (d) sodium bromostyrenesulfonate 0.01%, (e) sodium 4-(2-hydroxyethyl)benzenesulfonate 0.00% (however, it is the area ratio when the total of the HPLC peak areas of the above organic impurities and NaSS is taken as 100). That is, the content of sodium bromostyrenesulfonate in the high-purity NaSS was the same as in Example 12. However, as a result of quantifying the total bromine content, i.e., the bound bromine by combustion decomposition ion chromatography, it was 413 ppm, which was much higher than in Examples 12 to 14 (Table 5). This is considered to be due to the use of BEBS with a high content of nuclear brominated BEBS as a raw material. Hereinafter, in the same manner as in the examples, high-purity NaSS was polymerized to be induced to PSS, and the change in bromine ion concentration (the presence of unstable bound bromine) with time was confirmed.
[0148] <Production of Poly NaSS> The high-purity NaSS obtained above was polymerized under the same conditions as in Example 12 to obtain an aqueous solution of poly NaSS with a number average molecular weight Mn of 112,000 and a weight average molecular weight Mw of 285,000.
[0149] <Preparation and Stability Confirmation of PSS> The aqueous poly-NaSS solution obtained above was purified under the same conditions as in Example 12 to obtain 235.97 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight was 112,000, the weight average molecular weight was 285,000 (Mw / Mn = 2.54), the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. The PSS aqueous solution obtained above was aged and the change in bromide ion concentration was tracked. As shown in Table 5, it was revealed that the increase in bromide ions over time was remarkable compared to Examples 12 to 14. This is presumably because there is a large amount of bound bromine in NaSS, that is, because there are many nuclear brominated compounds contained in BEBS, which is the precursor.
[0150] Comparative Example 9 Synthesis of Sodium 4-Styrenesulfonate (5) <Synthesis of NaSS> Using the 72.1 wt%-BEBS aqueous solution obtained in Comparative Example 1 as a raw material, 325.46 g of wet crystals of NaSS were obtained under the same conditions as in Example 12 except for this.
[0151] <Purification of NaSS> The NaSS obtained above was subjected to ion exchange treatment under the same conditions as in Example 12 to obtain 32.50 g of high-purity NaSS crystals. The purity after drying was 99.5 wt%, the moisture was 0.5 wt%, the bromide ion was less than 1 ppm, and the total bromine content was 665 ppm. It is clear that the total bromine amount is large compared to Examples 12 to 14 (Table 5). This is presumably because BEBS containing a large amount of nuclear brominated BEBS was used as a raw material. Similar to Example 12, high-purity NaSS was polymerized to be induced into PSS, and the change in bromide ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0152] <Synthesis of Poly-NaSS> Using the high-purity NaSS obtained above, an aqueous poly-NaSS solution was obtained under the same conditions as in Example 12 except for this. The number average molecular weight Mn was 113,000, and the weight average molecular weight Mw was 291,000 (Mw / Mn = 2.56).
[0153] <Preparation and Stability Confirmation of PSS> Except for using the aqueous poly-NaSS solution obtained above, ultrafiltration and ion exchange treatment were carried out under the same conditions as in Example 12 to obtain 238.48 g of a 10.0 wt% PSS aqueous solution. The number average molecular weight was 113,000, the weight average molecular weight was 291,000, the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. The PSS aqueous solution obtained above was aged, and as a result of tracking the change in bromine ion concentration, as shown in Table 5, it was revealed that the increase in bromine ions over time was remarkable compared to Examples 12 to 14. This is considered to be because the amount of bound bromine in NaSS is large, that is, because the amount of nuclear brominated species contained in BEBS, which is the precursor, is large.
[0154] Comparative Example 10 Synthesis of Sodium 4-Styrenesulfonate (6) <Synthesis of NaSS> Except for using the 70.8 wt%-BEBS aqueous solution obtained in Comparative Example 2 as a raw material, 315.02 g of wet crystals of NaSS were obtained under the same conditions as in Example 12.
[0155] <Purification of NaSS> The NaSS obtained above was subjected to ion exchange treatment under the same conditions as in Example 12 to obtain 32.00 g of high-purity NaSS crystals. The purity after drying was 99.5 wt%, the water content was 0.5 wt%, the bromide ion was less than 1 ppm, and the total bromine content was 1264 ppm. It is clear that the total amount of bromine is large compared to Examples 12 to 14 (Table 5). This is considered to be because BEBS with a high content of nuclear brominated BEBS was used as a raw material. Similar to Example 12, NaSS was polymerized to be induced into PSS, and the change in bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0156] <Synthesis of Poly-NaSS> Except for using the high-purity NaSS obtained above, an aqueous poly-NaSS solution was obtained under the same conditions as in Example 12. The number average molecular weight Mn was 112,000, and the weight average molecular weight Mw was 283,000 (Mw / Mn = 2.53).
[0157] <Preparation and Stability Confirmation of PSS> Except for using the aqueous poly-NaSS solution obtained above, ultrafiltration and ion exchange treatment were carried out under the same conditions as in Example 12 to obtain 238.48 g of a 10.0 wt% PSS aqueous solution. The number average molecular weight was 112,000, the weight average molecular weight was 283,000 (Mw / Mn = 2.53), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above PSS aqueous solution was aged and the change in bromine ion concentration was traced. As a result, as shown in Table 5, it was clear that the increase in bromine ions over time was remarkable compared to Examples 12 to 14. This is presumably because the amount of bound bromine in NaSS is large, that is, because the amount of nuclear brominated species contained in BEBS, the precursor, is large.
[0158] Comparative Example 11 Synthesis of Sodium 4-Styrenesulfonate (7) <Synthesis of NaSS> Except for using the 72.3 wt%-BEBS aqueous solution obtained in Comparative Example 4 as a raw material, 327.31 g of wet crystals of NaSS were obtained under the same conditions as in Example 12.
[0159] <Purification of NaSS> The NaSS obtained above was subjected to ion exchange treatment under the same conditions as in Example 12 to obtain 31.60 g of high-purity NaSS crystals. The purity after drying was 99.4 wt%, the water content was 0.6 wt%, the bromide ion was less than 1 ppm, and the total bromine content was 4463 ppm. It was clear that the total bromine amount was large compared to Examples 12 to 14. This is presumably because BEBS containing a large amount of nuclear brominated BEBS was used as a raw material. Similar to Example 12, NaSS was polymerized to be induced into PSS, and the change in bromine ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0160] <Synthesis of Poly-NaSS> Except for using the high-purity NaSS obtained above, an aqueous poly-NaSS solution was obtained under the same conditions as in Example 12. The number average molecular weight Mn was 113,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.52).
[0161] <Preparation and Stability Confirmation of PSS> Except for using the aqueous solution of poly-NaSS obtained above, ultrafiltration and ion exchange treatment were carried out under the same conditions as in Example 12 to obtain 244.69 g of a 10.0 wt% aqueous solution of PSS. The number average molecular weight was 113,000, the weight average molecular weight was 285,000 (Mw / Mn = 2.52), the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above aqueous PSS solution was aged and the change in bromide ion concentration was tracked. As a result, as shown in Table 5, it is clear that the increase in bromide ions over time is remarkable compared to Examples 12 to 14. This is considered to be due to the large amount of bound bromine in NaSS, that is, the large amount of nuclear brominated compounds contained in BEBS, which is the precursor.
[0162] Comparative Example 12 Synthesis of Ethyl 4-Styrenesulfonate (4) <Synthesis of Ethyl 4-Styrenesulfonate> Except for using the high-purity NaSS obtained in Comparative Example 9 as a raw material, 11.80 g of ETSS was obtained by the same operation as in Example 15. The purity based on area% determined by gas chromatography was 93.0%. The bromine content in the ETSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 651 ppm, which is clearly higher in bromine content compared to Examples 15 to 17 (Table 5). This is considered to be due to using NaSS derived from BEBS with a large content of nuclear brominated BEBS as a raw material. Furthermore, by the following method, ETSS was polymerized to be induced into PSS, and the change in bromide ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0163] <Synthesis of Poly-ETSS> Except for using the ETSS obtained above as a raw material, ETSS was polymerized under the same conditions as in Example 15 to obtain poly-ETSS.
[0164] <Preparation and Stability Confirmation of PSS> Using the poly-ETSS obtained above as a raw material, 26.88 g of a 10.0 wt% PSS aqueous solution was obtained under the same conditions as in Example 15. The number average molecular weight was 9,000, the weight average molecular weight was 12,000 (Mw / Mn = 1.33), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above PSS aqueous solution was aged and the change in bromine ion concentration was tracked. As shown in Table 5, it was revealed that the increase in bromine ions over time was remarkable compared to Examples 15 to 17. This is presumably because the amount of bound bromine in ETSS is large, that is, because the amount of nuclear brominated compounds contained in BEBS, the precursor, is large.
[0165] Comparative Example 13 Synthesis of Ethyl 4-Styrenesulfonate (5) <Synthesis of ETSS> Using the high-purity NaSS obtained in Comparative Example 10 as a raw material, 11.90 g of ETSS was obtained under the same conditions as in Example 15. The purity based on area% determined by gas chromatography was 93.0%. The bromine content in the ETSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 1331 ppm, which was clearly higher in bromine content compared to Examples 15 to 17 (Table 5). This is presumably because NaSS derived from BEBS with a high content of nuclear brominated BEBS was used as a raw material. Furthermore, by the following method, ETSS was polymerized to be induced into PSS, and the change in bromine ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0166] <Synthesis of Poly-ETSS> Using the ETSS obtained above as a raw material, ETSS was polymerized under the same conditions as in Example 15 to obtain poly-ETSS.
[0167] <Preparation and Stability Confirmation of PSS> Using the poly-ETSS obtained above as a raw material, 26.99 g of a 10.0 wt% PSS aqueous solution was obtained in the same manner as in Example 15 except for this. The number average molecular weight was 9,000, the weight average molecular weight was 12,000 (Mw / Mn = 1.33), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above PSS aqueous solution was aged and the change in bromine ion concentration was traced. As a result, as shown in Table 5, it was revealed that the increase in bromine ions over time was remarkable compared to Examples 15 to 17. This is presumably because the amount of bound bromine in ETSS is large, that is, because the amount of nuclear brominated compounds contained in BEBS, which is the precursor, is large.
[0168] Comparative Example 14 Synthesis of Ethyl 4-Styrenesulfonate (6) <Synthesis of ETSS> Using the high-purity NaSS obtained in Comparative Example 11 as a raw material, 11.95 g of ETSS was obtained under the same conditions as in Example 15 except for this. The purity based on area% determined by gas chromatography was 94.0%. The bromine content in the ETSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 4,667 ppm. It was revealed that the bromine content was higher compared to Examples 15 to 17 (Table 5). This is presumably because NaSS derived from BEBS with a high content of nuclear brominated BEBS was used as a raw material. Furthermore, by the following method, ETSS was polymerized to be induced into PSS, and the change in bromine ion concentration (the presence of unstable bound bromine) over time was confirmed.
[0169] <Synthesis of Poly-ETSS> Using the ETSS obtained above as a raw material, ETSS was polymerized under the same conditions as in Example 15 except for this to obtain poly-ETSS.
[0170] <Preparation and Stability Confirmation of PSS> Using the poly-ETSS obtained above as a raw material, 26.10 g of a 10.0 wt% PSS aqueous solution was obtained in the same manner as in Example 15. The number average molecular weight was 9,000, the weight average molecular weight was 11,000 (Mw / Mn = 1.22), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. The above PSS aqueous solution was aged and the bromine ion concentration was tracked. As shown in Table 5, it was revealed that the increase in bromine ions over time was remarkable compared to Examples 15 to 17. This is presumably because the amount of bound bromine in ETSS is large, that is, because the amount of nuclear brominated compounds contained in BEBS, the precursor, is large.
[0171] Comparative Example 15 Synthesis of Neopentyl 4-Styrenesulfonate (2) <Synthesis of NPSS> A ClSS solution was prepared under the same conditions as in Example 15, such as the charged weight, except that the high-purity NaSS obtained in Comparative Example 9 was used as a raw material, and 35.10 g of white crystals of NPSS were obtained under the same conditions as in Example 18. The yield based on ClSS was 24%, 1 The purity determined by 1H-NMR (internal standard substance 1,3,5-trimethylbenzene) was 97.3%. The bromine content in the NPSS determined by ion chromatography, that is, the inorganic bromine content extracted with pure water, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 649 ppm, which was clearly higher in bromine content than in Example 18 (Table 5). This is presumably because NaSS derived from BEBS with a high content of nuclear brominated BEBS was used as a raw material. Similar to Example 18, NPSS was polymerized to derive PSS, and the change in bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0172] <Synthesis of Poly-NPSS> Using the NPSS obtained above as a raw material, 6.99 g of poly-NPSS (yield based on NPSS was 71%) was obtained in the same manner as in Example 18.
[0173] <Preparation and Stability Confirmation of PSS> Using the poly-NPSS obtained above as a raw material, the same operations as in Example 18 were performed in all other respects to obtain 57.32 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight was 9,000, the weight average molecular weight was 11,000 (Mw / Mn = 1.22), the bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above PSS aqueous solution was aged and the bromine ion concentration was tracked. As a result, as shown in Table 5, it was clear that the increase in bromine ions over time was significant compared to Example 18. This is presumably because the amount of bound bromine in NPSS is large, that is, because there are many nuclear brominated compounds that may be contained in the precursor BEBS.
[0174] Comparative Example 16 Production of Sodium 4-Styrenesulfonyl(trifluoromethylsulfonylimide) (TfNS-Na) (2) <Synthesis of TfNS-Na> Using the high-purity NaSS obtained in Comparative Example 9 as a raw material, 24.65 g of TfNS-Na was obtained (yield 73%) by the same operations as in Example 19 in all other respects.
[0175] <Purification of TfNS-Na> The TfNS-Na obtained above was ion-exchanged by the same operation as in Example 19 and neutralized with sodium hydroxide to obtain 20.60 g of crystals of high-purity TfNS-Na. 1 The purity after drying determined by 1H-NMR (internal standard substance 1,3,5-trimethylbenzene) was 98.3 wt%, the water content was 1.5 wt%, the bromine ion concentration determined by ion chromatography was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 642 ppm. It was clear that the amount of bound bromine was large compared to Example 19 (Table 5). This is presumably because NaSS derived from BEBS with a high content of nuclear brominated BEBS was used as a raw material. Similar to Example 19, TfNS-Na was induced to poly-TfNS-H and the change in bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0176] <Preparation and Stability Confirmation of Poly-TfNS-H> Except for using the TfNS-Na obtained above, poly-TfNS-Na was synthesized under the same conditions as in Example 19. The polymerization conversion rate was 98.7%, the number average molecular weight was 35,000, and the weight average molecular weight was 82,000 (Mw / Mn = 2.34). Subsequently, by performing ultrafiltration and ion exchange treatment under the same conditions as in Example 19, 149.79 g of a 10 wt% aqueous solution of poly-TfNS-H was obtained. The bromine ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, the above poly-TfNS aqueous solution was aged and the bromine ion concentration was traced. As a result, as shown in Table 5, it is clear that the increase in bromine ions over time is remarkable compared to Example 19. This is presumably because the amount of bound bromine in TfNS-Na is large, that is, because there are many nuclear brominated compounds that may be contained in BEBS, which is the precursor.
[0177] Comparative Example 17 Production of Lithium 4-Styrenesulfonate (2) <Synthesis of LiSS> Except for using the 72.3 wt%-BEBS aqueous solution of Comparative Example 4 as a raw material, 203.50 g of a wet cake of LiSS was obtained under the same conditions as in Example 20.
[0178] <Purification of LiSS> The above LiSS was purified under the same conditions as in Example 20 to obtain 73.50 g of dry LiSS. The purity was 98.6 wt%, the moisture was 1.40 wt%, the bromine ions were less than 1 ppm, and the total bromine content was 4339 ppm. It is clear that the total bromine amount is larger compared to Example 20 (Table 5). This is presumably because there were many nuclear brominated BEBS in the BEBS used as the raw material. Similar to Example 20, LiSS was polymerized to induce PSS, and an increase in the bromine ion concentration over time (the presence of unstable bound bromine) was confirmed.
[0179] <Synthesis of Poly-LiSS> Except for using the LiSS obtained above, polymerization was carried out under the same conditions as in Example 20. The polymerization conversion rate was 99.7%, the number average molecular weight was 39,000, and the weight average molecular weight was 91,000 (Mw / Mn = 2.33).
[0180] <Preparation and Stability Confirmation of PSS> The obtained aqueous poly-LiSS solution was subjected to ultrafiltration and ion exchange treatment under the same conditions as in Example 20 to obtain 242.56 g of a 10.0 wt% PSS aqueous solution. The bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 20, the obtained PSS aqueous solution was aged, and the bromide ion concentration was traced. As shown in Table 5, it is clear that the increase in bromide ions over time is greater compared to Example 20. This is presumably because the amount of bound bromine in LiSS is large, that is, because there are many nuclear brominated compounds that may be contained in BEBS, which is the precursor.
[0181] Comparative Example 18 Production of Lithium Bis-(4-styrenesulfonyl)imide (BVBSI-Li) <Synthesis of 4-Vinylbenzenesulfonamide> Using the ClSS solution synthesized in Comparative Example 14 as a raw material, 6.10 g (yield 66%) of a white solid of 4-styrenesulfonamide was obtained under the same conditions as in Example 23, such as the charged weight.
[0182] <Synthesis of BVBSI-Li> Using the 4-styrenesulfonamide obtained above and the ClSS solution synthesized in Comparative Example 14, 6.25 g of white crystals of BVBSI-Li were obtained under the same conditions as in Example 23, such as the charged weight. The yield based on ClSS was 60%. 1 The purity determined by 1H-NMR (internal standard substance 1,3,5-trimethylbenzene) was 93.3%. The bromine content in the high-purity BVBSI-Li determined by ion chromatography, that is, the inorganic bromine content analyzed in an aqueous solution, was less than 1 ppm, and the total bromine content determined by combustion decomposition ion chromatography was 4556 ppm.
[0183] Example 24 Production of Polystyrenesulfonic Acid (PSS) (1) <Synthesis of Poly-NaSS> In Example 12, after polymerizing high-purity NaSS, instead of adding 1.64 g of a 48 wt% sodium hydroxide aqueous solution and heating at 60°C for 24 hours under a nitrogen stream, 1.65 g of a 48 wt% sodium hydroxide aqueous solution and 1.86 g of sodium hypophosphite monohydrate were added, and stirring was continued at 110°C for 15 hours while maintaining the solution pH ≥ 13 or higher to obtain an aqueous poly-NaSS solution. The number average molecular weight Mn of poly-NaSS was 114,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.50).
[0184] <Preparation and Stability Confirmation of PSS> The above aqueous poly-NaSS solution was purified by the same operation as in Example 12 to obtain 230.05 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight was 114,000, the weight average molecular weight was 282,000 (Mw / Mn = 2.47), the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. Similar to Example 12, PSS solid was obtained and the halogen content was analyzed. As a result, the total bromine content was 63 ppm, which was decreased compared to Example 12. It is considered that a part of the bound bromine was released by appropriately performing chemical treatment before purifying poly-NaSS. In addition, the total chlorine content in the PSS solid was less than 1 ppm. Similar to Example 12, the above 10 wt% PSS aqueous solution was aged at 70°C, and the change in the bromide ion concentration was tracked. As shown in Table 5, it is clear that the increase in bromide ions over time is further suppressed compared to Example 12.
[0185] Example 25 Production of Polystyrenesulfonic Acid (PSS) (2) <Synthesis of Poly-NaSS> In Example 13, after polymerizing high-purity NaSS, instead of adding 1.64 g of a 48 wt% sodium hydroxide aqueous solution and heating at 60°C for 24 hours under a nitrogen stream, 1.65 g of a 48 wt% sodium hydroxide aqueous solution was added, and stirring was continued at 110°C for 20 hours while maintaining the solution pH ≥ 13 to obtain an aqueous poly-NaSS solution. The number average molecular weight Mn of poly NaSS was 114,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.50).
[0186] <Preparation and Stability Confirmation of PSS> The aqueous poly NaSS solution obtained above was purified by the same operation as in Example 13, and 231.30 g of a 10.00 wt% PSS aqueous solution was obtained. The number average molecular weight of PSS was 112,000, the weight average molecular weight was 281,000 (Mw / Mn = 2.51), the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. PSS solid was obtained in the same manner as in Example 12, and as a result of analyzing the total bromine content, it was 35 ppm, which was lower than that in Example 13. It is considered that a part of the bound bromine was released by appropriate chemical treatment before purifying poly NaSS. In addition, the total chlorine content in the PSS solid was less than 1 ppm. Similar to Example 13, the above 10 wt% PSS aqueous solution was aged at 70 °C, and the change in bromide ion concentration was traced. As shown in Table 5, it is clear that the increase in bromide ions over time was further suppressed compared to Example 13.
[0187] Example 26 Production of Polystyrene Sulfonic Acid (PSS) (3) <Synthesis of Poly NaSS> In Example 14, after polymerizing high-purity NaSS, instead of adding 1.64 g of a 48 wt% sodium hydroxide aqueous solution and heating at 60 °C for 24 hours under a nitrogen stream, 2.01 g of a 48 wt% sodium hydroxide aqueous solution and 1.90 g of sodium hypophosphite monohydrate were added, and stirring was continued at 110 °C for 15 hours while maintaining the solution pH ≥ 13 to obtain an aqueous poly NaSS solution. The number average molecular weight Mn of poly NaSS was 114,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.50).
[0188] <Preparation and Stability Confirmation of PSS> The aqueous poly-NaSS solution obtained above was purified by the same operation as in Example 14 to obtain 232.02 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight of PSS was 113,000, the weight average molecular weight was 282,000 (Mw / Mn = 2.50), the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. PSS solid was obtained in the same manner as in Example 12, and the total bromine content was analyzed, and the result was 91 ppm, which was lower than that in Example 14. It is considered that a part of the bound bromine was released by appropriate chemical treatment before purifying the poly-NaSS. In addition, the total chlorine content was less than 1 ppm. Similar to Example 14, the above 10 wt% PSS aqueous solution was aged at 70 °C, and the change in bromide ion concentration was traced. As a result, as shown in Table 5, it is clear that the increase in bromide ions over time is further suppressed compared to Example 14. It is considered that a part of the bound bromine was released by appropriate chemical treatment before purifying the poly-NaSS.
[0189] Example 27 Production of styrenesulfonic acid / styrene (SS / St) copolymer <Synthesis of NaSS / styrene copolymer> In Example 21, 1.65 g of a 48 wt% aqueous sodium hydroxide solution was added to a 15 wt% NaSS / styrene copolymer aqueous solution before purification under a nitrogen stream, and the mixture was stirred at 90 °C for 24 hours while maintaining the solution pH ≥ 13 to obtain a NaSS / styrene copolymer aqueous solution. The number average molecular weight Mn of the copolymer was 33,000, and the weight average molecular weight Mw was 74,000 (Mw / Mn = 2.24).
[0190] <Preparation and stability confirmation of PSS> The NaSS / styrene copolymer obtained above was purified by the same operation as in Example 21 to obtain 229.50 g of a 10.00 wt% styrenesulfonic acid / styrene copolymer aqueous solution. The number average molecular weight Mn of the acid-type copolymer was 33,000, the weight average molecular weight Mw was 74,000 (Mw / Mn = 2.24), the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. The 10 wt% copolymer aqueous solution was aged at 70 °C, and the change in bromide ion concentration was traced. As shown in Table 5, it is clear that the increase in bromide ions over time is further suppressed compared to Example 21. It is considered that a part of the bound bromine was released by appropriate chemical treatment before purifying the polymer.
[0191] Example 28 Production of styrenesulfonic acid / methacrylic acid (SS / MAA) copolymer <Synthesis of NaSS / methacrylic acid copolymer> In Example 22, 5.00 g of a 48 wt% sodium hydroxide aqueous solution was added to a 15 wt% NaSS / MAA copolymer aqueous solution before purification under a nitrogen stream, and stirring was continued at 90 °C for 24 hours while maintaining the solution at pH ≥ 13 to obtain a NaSS / methacrylic acid copolymer. The number average molecular weight was 46,000, and the weight average molecular weight was 129,000 (Mw / Mn = 2.80).
[0192] <Synthesis and stability confirmation of styrenesulfonic acid / methacrylic acid copolymer> The above-mentioned NaSS / methacrylic acid copolymer was subjected to ultrafiltration and ion exchange treatment under the same conditions as in Example 22 to obtain 258.06 g of a 10.0 wt% aqueous solution of styrenesulfonic acid / methacrylic acid copolymer. The bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. The solid of the styrenesulfonic acid / methacrylic acid copolymer was obtained in the same manner as in Example 12, and the total bromine content was analyzed. The result was 45 ppm, and the total chlorine content was less than 1 ppm.
[0193] <Stability of styrenesulfonic acid / methacrylic acid copolymer> Similar to Example 22, the 10 wt% styrenesulfonic acid / methacrylic acid copolymer aqueous solution was aged at 70 °C, and the change in bromide ion concentration was traced. As shown in Table 5, it is clear that the increase in bromide ions over time is further suppressed compared to Example 22. It is considered that a part of the bound bromine was released by appropriate chemical treatment before purifying the polymer.
[0194] Example 29 Production of Polystyrene Sulfonic Acid (PSS) (4) <Synthesis of Poly NaSS> In Example 12, after polymerizing high purity NaSS, instead of adding 1.64 g of a 48 wt% aqueous sodium hydroxide solution and heating at 60°C for 24 hours under a nitrogen stream, 0.50 g of sodium formate and 0.05 g of palladium carbon (Pd content 5 wt%) were added, and stirring was continued at 90°C for 24 hours as it was. Thereafter, the polymer solution was filtered through a membrane filter with a pore size of 0.45 μm to remove palladium carbon. The number average molecular weight Mn of poly NaSS was 114,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.50).
[0195] <Preparation of PSS and Confirmation of Stability> The aqueous poly NaSS solution obtained above was purified by the same operation as in Example 12 to obtain 230.36 g of a 10.00 wt% PSS aqueous solution. The number average molecular weight of PSS was 114,000, the weight average molecular weight was 282,000, the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. A solid of the copolymer was obtained in the same manner as in Example 12, and as a result of analyzing the total bromine content, it was 51 ppm, and the total chlorine content was less than 1 ppm. Similar to Example 12, the above 10 wt% PSS aqueous solution was aged at 70°C, and as a result of tracking the change in bromide ion concentration, as shown in Table 5, it is clear that the increase in bromide ions over time is further suppressed compared to Example 14. It is considered that this is because a part of the bound bromine was liberated by the chemical treatment of poly NaSS.
[0196] Comparative Example 19 Production of Polystyrene Sulfonic Acid (5) <Synthesis of Poly NaSS> In Comparative Example 11, after polymerizing high-purity NaSS, instead of adding 1.64 g of a 48 wt% sodium hydroxide aqueous solution and heating at 60°C for 24 hours under a nitrogen stream, 2.02 g of a 48 wt% sodium hydroxide aqueous solution was added and stirred at 110°C for 15 hours while maintaining the solution pH ≥ 13 to obtain an aqueous poly-NaSS solution. The number average molecular weight Mn was 113,000, and the weight average molecular weight Mw was 285,000 (Mw / Mn = 2.52).
[0197] <Preparation and Stability Confirmation of PSS> Except for using the aqueous poly-NaSS solution obtained above, ultrafiltration and ion exchange treatment were performed under the same conditions as in Comparative Example 11 to obtain 240.61 g of a 10.0 wt% PSS aqueous solution. The number average molecular weight was 113,000, the weight average molecular weight was 283,000, the bromide ion concentration was less than 1 ppm, and the sodium content was less than 1 ppm. PSS solid was obtained in the same manner as in Example 12, and as a result of analyzing the total bromine content, it was 2721 ppm, and the total chlorine content was less than 1 ppm. Similar to Comparative Example 11, the above 10 wt% PSS aqueous solution was aged, and the change in bromide ion concentration was tracked. As shown in Table 5, the increase in bromide ions over time was halved compared to Comparative Example 11, but it was clearly significantly larger compared to Examples 12 to 14 and Example 25. Although poly-NaSS was chemically treated under appropriate conditions, it is considered that the amount of bound bromine in NaSS was too large, that is, the amount of nuclear brominated compounds contained in BEBS, which is the precursor, was too large.
[0198]
Table 5
[0199] Example 30 Production of Polystyrene Sulfonic Acid Composition (1) Hydroquinone (700 ppm relative to the pure polymer content) was added to the 10 wt % styrene sulfonic acid / styrene copolymer aqueous solution obtained in Example 27, and the solution was divided into small sample bottles, sealed, and aged in an oven at 70°C to monitor changes in molecular weight and bromine ion concentration. As a result, as shown in Table 6, it is clear that the increase in bromine ions was small and that the decrease in molecular weight was significantly suppressed compared to Comparative Example 20.
[0200] Example 31 Preparation of polystyrene sulfonic acid composition (2) 4-Methoxyphenol (1500 ppm relative to the pure polymer content) was added to the 10 wt % styrene sulfonic acid / styrene copolymer aqueous solution obtained in Example 27, and changes in the weight average molecular weight and bromine ion concentration were monitored in the same manner as in Example 30. As a result, as shown in Table 6, it is clear that the increase in bromine ions was small and that the decrease in molecular weight was significantly suppressed compared to Comparative Example 20.
[0201] Comparative Example 20: Production of polystyrene sulfonic acid composition (3) 4-Methoxyphenol (10 ppm relative to the pure polymer content) was added to the 10 wt % styrene sulfonic acid / styrene copolymer aqueous solution obtained in Example 27, and changes in the weight-average molecular weight and bromine ion concentration were monitored in the same manner as in Example 30. As a result, as shown in Table 6, it is clear that although the increase in bromine ions was small, the decrease in molecular weight was significant compared to Examples 30 and 31.
[0202] [Table 6] [Industrial Applicability]
[0203] The 4-(2-bromoethyl)benzenesulfonic acid of the present invention having reduced nuclear bromine content is useful as a precursor for producing styrenesulfonic acids having reduced bound bromine content and polymers thereof. The styrenesulfonic acids having reduced bound bromine content and polymers thereof are extremely useful as modifiers for secondary batteries, dopants for conductive polymers, additives for semiconductor polishing agents and cleaning agents, photoresists, organic EL devices, and other applications, particularly in electrical materials. [Explanation of symbols]
[0204] A: 4-(2-hydroxyethyl)benzenesulfonic acid peak B: BEBS parabody peak C: BEBS orthogonal peak D: 4-(1-bromoethyl)benzenesulfonic acid peak E: 2-bromo-4-(2-bromoethyl)benzenesulfonic acid (nuclear brominated BEBS) Peak a: Peak position of sodium orthostyrene sulfonate b: Peak position of sodium 4-(2-bromoethyl)benzenesulfonate c: Peak position of sodium meta-styrenesulfonate d: Peak position of sodium bromostyrene sulfonate e: Peak position due to sodium 4-(2-hydroxyethyl)benzenesulfonate
Claims
1. The content of nuclear brominated 2-bromoethylbenzenesulfonic acid represented by the following general formula (A) relative to 4-(2-bromoethyl)benzenesulfonic acid is 0.10% or less (wherein this is the peak area % determined by liquid chromatography (LC), and the peak area % of nuclear brominated 2-bromoethylbenzenesulfonic acid is calculated when the peak area of 4-(2-bromoethyl)benzenesulfonic acid is taken as 100%), The purity of 4-(2-bromoethyl)benzenesulfonic acid determined by liquid chromatography (LC) is 93 area % or more. High purity 4-(2-bromoethyl)benzenesulfonic acid composition. 【Chemistry 17】
2. The high purity 4-(2-bromoethyl)benzenesulfonic acid composition according to claim 1, wherein the nuclear brominated 2-bromoethylbenzenesulfonic acid is 2-bromo-4-(2-bromoethyl)benzenesulfonic acid.
3. A high-purity styrene sulfonic acid composition represented by the following general formula (B), having a bound bromine content of 400 ppm or less as determined by combustion decomposition ion chromatography (CIC): 【Chemistry 18】 [In the formula, R 1 represents the following general formula (C), the following general formula (D), an amino group, or a chlorine atom.] 【Chemistry 19】 [In the formula, R 2 represents a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a hydrogen atom, an alkali metal, a substituted or unsubstituted ammonium cation, or a substituted or unsubstituted phosphonium cation.] 【Chemistry 20】 [In the formula, R 3 represents a substituted or unsubstituted alkyl group, a hydrogen atom, an alkali metal, or a substituted or unsubstituted ammonium cation, and R 4 represents a trifluoromethylsulfonyl group, a perfluorobutylsulfonyl group, a fluorosulfonyl group, a trifluoromethylacetyl group, or a 4-ethenylphenylsulfonyl group.]
4. A high-purity styrenesulfonic acid composition, wherein the styrenesulfonic acid represented by the following general formula (B') is sodium 4-styrenesulfonate, lithium 4-styrenesulfonate, potassium 4-styrenesulfonate, ammonium 4-styrenesulfonate, N,N-dimethylcyclohexylamine 4-styrenesulfonate, trioctyl 4-styrenesulfonate, 4-styrenesulfonyl chloride, 4-styrenesulfonamide, ethyl 4-styrenesulfonate, neopentyl 4-styrenesulfonate, 4-styrenesulfonyl(trifluoromethylsulfonylimide), 4-styrenesulfonyl(perfluorobutylsulfonylimide), 4-styrenesulfonyl(fluorosulfonylimide) or lithium bis-(4-styrenesulfonyl)imide, and the bound bromine content determined by combustion decomposition ion chromatography (CIC) is 400 ppm or less. 【Chemistry 21】 (In the formula, R 1 is the same as R 1 in the general formula (B) described in claim 3.)
5. A polystyrene sulfonic acid composition having reduced bound bromine, comprising polystyrene sulfonic acids having the following repeating structural unit (E), or polystyrene sulfonic acids having the following repeating structural unit (E) and the following repeating structural unit (F), wherein a 10 wt % aqueous solution of the polystyrene sulfonic acids has a bromine ion concentration of 30 ppm or less when the aqueous solution is maintained at 70°C for 20 days. 【Chemical 22】 (In the formula, R 1 is the same as R 1 in the general formula (B) described in claim 3.) 【Chemistry 23】 [In the formula, Q represents a repeating structural unit derived from a vinyl monomer copolymerizable with styrenesulfonic acids.]
6. The polystyrene sulfonic acid composition according to claim 5, wherein the number average molecular weight of the polystyrene sulfonic acid is 500 to 5,000,000.
7. The polystyrene sulfonate composition according to claim 5 or claim 6, wherein Q in the repeating structural unit (F) contains a repeating structural unit derived from a vinyl monomer which is one or a combination of two or more selected from the group consisting of (meth)acrylic acid, a (meth)acrylic acid ester, a (meth)acrylamide, an N-substituted maleimide, a styrene, and a vinylpyridine.
8. The polystyrene sulfonic acid composition according to any one of claims 5 to 7, wherein Q in the repeating structural unit (F) includes a repeating structural unit derived from a crosslinkable monomer which is one or a combination of two or more selected from the group consisting of substituted styrenes, (meth)acrylic acid esters, (meth)acrylamides, and N-substituted maleimides.
9. A polystyrene sulfonic acid composition according to any one of claims 5 to 8, in which the bromide ion concentration in a 10 wt % aqueous solution when kept at 70°C for 20 days is 10 ppm or less.
10. An aqueous solution composition comprising the polystyrene sulfonic acid composition according to any one of claims 5 to 9 and a phenol-based antioxidant, The content of the phenol-based antioxidant relative to the pure content of the polystyrene sulfonic acids is 20 ppm to 2,000 ppm. Aqueous solution composition of polystyrene sulfonic acids.
11. The polystyrene sulfonic acid aqueous solution composition according to claim 10, wherein the phenolic antioxidant is at least one selected from the group consisting of 2-methoxyphenol, 3-methoxyphenol, 4-methoxyphenol, 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol, 2,6-di-tert-butyl-4-methylphenol, 4-tert-butylcatechol, hydroquinone and methoxyhydroquinone.